Recycled water-absorbing resin composition

JP2025025590APending Publication Date: 2025-02-21NIPPON SHOKUBAI CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2023130471
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-09
Publication Date
2025-02-21

AI Technical Summary

Benefits of technology

【0012】 本発明の一態様によれば、優れた吸水速度を有するリサイクル吸水性樹脂組成物を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025025590000001
    Figure 2025025590000001
  • Figure 2025025590000002
    Figure 2025025590000002
  • Figure 2025025590000003
    Figure 2025025590000003
Patent Text Reader

Abstract

To provide a recycled water-absorbing resin composition with an enhanced water absorption rate.SOLUTION: A recycled water-absorbing resin composition comprises: a water-absorbing resin; a specific amount of at least one polyvalent metal cation selected from the group consisting of calcium ions, magnesium ions, and aluminum ions; and a specific amount of a metal chelating agent (excluding monovalent carboxylic acids (salts) consisting only of CHO and polyvalent carboxylic acids (salts) consisting only of CHO).SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a recycled water-absorbent resin composition. [Background technology]

[0002] In recent years, absorbent resins have been widely used as water absorbents in absorbent articles such as paper diapers, sanitary napkins, and incontinence pads, as constituent materials thereof, from the viewpoint of absorbing body fluids. Examples of such absorbent resins include hydrolyzates of starch-acrylonitrile graft copolymers, neutralized products of starch-acrylic acid graft polymers, saponified products of vinyl acetate-acrylic acid ester copolymers, and crosslinked products of partially neutralized acrylic acid polymers. Among them, from the viewpoint of water absorption performance, polyacrylic acid (salt)-based absorbent resins using acrylic acid and / or its salt as a monomer are most widely produced industrially, and many technologies related to such absorbent resins have been disclosed.

[0003] Although absorbent articles are generally disposable, interest in recycling absorbent articles is increasing due to the rise in environmental awareness. Known techniques for recycling absorbent resins used in absorbent articles include a technique in which a superabsorbent polymer derived from used absorbent articles is inactivated, treated with ozone water, then reactivated with an alkaline aqueous solution, and then hydrophilic fine particles are added and dried (Patent Document 1), a technique in which an alkali metal ion source is added to a regeneration aqueous solution containing a superabsorbent polymer inactivated by acid, and the resulting wet superabsorbent recycled polymer is dried (Patent Document 2), a technique having a step of obtaining a superabsorbent polymer that has been primarily dehydrated by immersing a sanitary product component material containing a superabsorbent polymer in an acid-containing aqueous solution, and a step of contacting the primarily dehydrated superabsorbent polymer with a polyvalent metal ion source (Patent Document 3), and a technique in which used superabsorbent polymer is dehydrated, and then a particle group of the superabsorbent polymer is attached, and then dried to suppress adhesion and coloring of the particles to each other (Patent Document 4). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] International Publication No. WO2020 / 241025 [Patent Document 2] International Publication No. WO2019 / 151538 [Patent Document 3] International Publication No. WO2023 / 007871 [Patent Document 4] International Publication No. WO2021 / 205780 Summary of the Invention [Problem to be solved by the invention]

[0005] However, the recycled water-absorbent resins in the conventional techniques as described above have room for improvement in terms of water absorption speed.

[0006] In the above-mentioned circumstances, one aspect of the present invention is to provide a recycled water-absorbent resin composition having an excellent water absorption rate. [Means for solving the problem]

[0007] In order to solve the above problems, one embodiment of the present invention includes the following configuration.

[0008] [1] A recycled water absorbent resin composition, comprising: (i) a water absorbent resin; and (ii) relative to 100% by mass of the recycled water absorbent resin composition, (ii-1) 0.001% by mass or more and 1.0% by mass or less of one or more polyvalent metal cations selected from the group consisting of calcium ions, magnesium ions, and aluminum ions, and (ii-2) 0.01% by mass or more and 5.0% by mass or less of a metal chelating agent (excluding a monovalent carboxylic acid (salt) consisting of only CHO and a polyvalent carboxylic acid (salt) consisting of only CHO).

[0009] [2] The recycled water-absorbent resin composition according to [1], wherein the water-absorbent resin comprises a plurality of types of water-absorbent resins.

[0010] [3] The recycled water absorbent resin composition according to [1] or [2], wherein the content of the metal chelating agent is from 2 times to 1000 times the total mass of the polyvalent metal cations.

[0011] [4] The recycled water-absorbing resin composition according to any one of [1] to [3], further comprising p-methoxyphenol. Effect of the Invention

[0012] According to one aspect of the present invention, a recycled water-absorbent resin composition having an excellent water absorption rate can be provided. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] <1. Recycled water-absorbent resin composition> [1-1] Technical concept of one embodiment of the present invention The present inventors have conducted research on (1) recycled water absorbent resins (compositions) obtained by recycling water absorbent resins recovered from used absorbent articles and / or water absorbent resins recovered from waste generated in the manufacturing process of water absorbent resins, and (2) recycled water absorbent resins (compositions) obtained by using, as part of a raw material, water absorbent resins recovered from used absorbent articles and / or water absorbent resins recovered from waste generated in the manufacturing process of water absorbent resins. In the process, the present inventors have found that such recycled water absorbent resin compositions may have poor water absorption speed. Water absorbent resins with poor water absorption speed have a problem of being unsuitable for product applications.

[0014] The present inventors speculated that the deterioration of the water absorption rate as described above is due to the presence of residual substances derived from body fluids such as human waste and / or polyvalent metal cations derived from compounds used in the manufacturing process of the water absorbent resin in the recycled water absorbent resin composition. As a result of intensively studying the above-mentioned problems based on such speculation, the present inventors found that the recycled water absorbent resin composition containing a metal chelating agent can be a recycled water absorbent resin composition having an excellent water absorption rate, and have completed the present invention. Such a recycled water absorbent resin composition having an excellent water absorption rate is comparable to a normal (unused) water absorbent resin and can be suitably used for product applications (for example, sanitary material applications).

[0015] [1-2] Recycled water-absorbent resin composition In one embodiment of the present invention, there is provided a recycled water absorbent resin composition, which comprises (i) a water absorbent resin, and (ii) (ii-1) 0.001% by mass to 1.0% by mass of one or more polyvalent metal cations selected from the group consisting of calcium ions, magnesium ions, and aluminum ions, and (ii-2) 0.01% by mass to 5.0% by mass of a metal chelating agent (excluding monovalent carboxylic acid (salt) consisting of only CHO and polyvalent carboxylic acid (salt) consisting of only CHO) relative to 100% by mass of the recycled water absorbent resin composition. Hereinafter, the "recycled water absorbent resin composition according to one embodiment of the present invention" may be referred to as "the present recycled water absorbent resin composition". "Consisting only of CHO" means "consisting only of carbon element, hydrogen element, and oxygen element".

[0016] The recycled water absorbent resin composition has an advantage of having an excellent water absorption rate. The "water absorption rate" of the water absorbent resin (recycled water absorbent resin) can be measured or evaluated by the method described in the Examples.

[0017] The present recycled water absorbent resin composition is preferably excellent in one or more properties selected from the group consisting of color tone (e.g., YI value and color), water-soluble content, and durability. The present recycled water absorbent resin composition is preferably almost odorless or completely odorless. The "color tone" ("YI value" and "color"), "water-soluble content", "durability", "water absorption rate", and "odor" of the water absorbent resin (recycled water absorbent resin) can be measured or evaluated by the methods described in the Examples.

[0018] In the present specification, the term "recycled water absorbent resin" or "recycled water absorbent resin composition" means, for example, any one of the following (1) to (3): (1) A recycled water-absorbent resin or a recycled water-absorbent resin composition produced by using, as a part of a raw material, a water-absorbent resin containing a liquid to be absorbed, such as human waste, recovered from used absorbent articles, and / or a solubilized polymer derived from a water-absorbent resin recovered from waste generated in the process of producing the water-absorbent resin; (2) A recycled water-absorbent resin or a recycled water-absorbent resin composition obtained by recycling a water-absorbent resin containing a liquid to be absorbed, such as human waste, recovered from used absorbent articles and / or a water-absorbent resin recovered from waste generated in the process of producing the water-absorbent resin, for an application requiring a water-absorbing function; (3) A recycled water-absorbent resin composition produced by using the recycled water-absorbent resin composition of (2) above as a part of a raw material.

[0019] In this specification, the water-absorbing resin recovered from such used absorbent articles and / or waste generated in the manufacturing process of the water-absorbing resin may be referred to as a "recovered water-absorbing resin." In addition, the recovered water-absorbing resin may include a water-absorbing resin contained in a water-absorbing article that was discarded before use.

[0020] Usually, the recovered water absorbent resin does not have water absorption performance or may have very low water absorption performance, and may contain a large amount of impurities derived from body fluids or generated during the manufacturing process of the water absorbent resin. Therefore, the recovered water absorbent resin is not used for product applications such as absorbent articles, but is disposed of, thermally recycled as fuel, composted, or otherwise disposed of. On the other hand, a "recycled water absorbent resin" or a "recycled water absorbent resin composition" is a water absorbent resin or water absorbent resin composition that uses a solubilized polymer of a recovered water absorbent resin as part of the raw material, and has an excellent water absorption rate and can be used for product applications such as absorbent articles (above (1)), or is a water absorbent resin or water absorbent resin composition that is derived from a recovered water absorbent resin but has the water absorption performance of the recovered water absorbent resin restored so that it can be used again for water absorption purposes (above (2) and (3)). The "recycled water absorbent resin" or "recycled water absorbent resin composition" in the above (2) and (3) can be said to be, in other words, a water absorbent resin or a water absorbent resin composition made from a recycled water absorbent resin as a raw material, which has water absorption performance and can be used for product applications such as absorbent articles.

[0021] [1-2-1] Absorbent articles In this specification, the term "absorbent article" refers to an article used for absorbing water. An example of the "absorbent article" is an absorbent article having an absorbent body containing a water-absorbing resin and a fibrous material, a top sheet having liquid permeability, and a back sheet having liquid impermeability. The absorbent body is preferably manufactured by blending the water-absorbing resin with the fibrous material, or by sandwiching the water-absorbing resin between the fibrous material and molding it into a shape such as a film, a tube, or a sheet. Here, the fibrous material may be hydrophilic fiber, such as pulverized wood pulp, cotton linters, crosslinked cellulose fiber, rayon, cotton, wool, acetate, vinylon, etc. Specific examples of the "absorbent article" include sanitary materials (sanitary products) such as paper diapers, sanitary napkins, adult incontinence products (incontinence pads), and pet sheets, but are not limited thereto.

[0022] In this specification, the term "used absorbent article" refers to an absorbent article (particularly, a sanitary material) that has absorbed any liquid (absorbed liquid), particularly bodily fluids such as urine and blood.

[0023] [1-2-2] Water-absorbing resin In this specification, the term "water-absorbent resin" refers to a water-swellable, water-insoluble polymer gelling agent, and generally refers to a conventional water-absorbent resin having a water absorption capacity of 10 to 1000 times its volume. More specifically, it is preferable that the water-absorbent resin before absorbing the liquid to be absorbed satisfies the physical property of CRC of 5 g / g or more as "water-swellable" specified in ERT441.2-02, and satisfies the physical property of Ext (water-soluble content) of 0 to 50 mass% as "water-insoluble" specified in ERT470.2-02.

[0024] Specific examples of water-absorbent resins include polyacrylic acid (salt)-based resins, polysulfonic acid (salt)-based resins, maleic anhydride (salt)-based resins, polyacrylamide-based resins, polyvinyl alcohol-based resins, polyethylene oxide-based resins, polyaspartic acid (salt)-based resins, polyglutamic acid (salt)-based resins, polyalginic acid (salt)-based resins, starch-based resins, and cellulose-based resins.

[0025] [1-2-3] Waste generated during the manufacturing process of water-absorbent resin In this specification, the term "waste generated during the manufacturing process of a water-absorbent resin" refers to a water-absorbent resin that is generated during the manufacturing process of a water-absorbent resin and is rejected from product use for some reason (for example, because its water-absorbing properties, color tone, etc. are not within the standard), and is usually discarded, and is therefore referred to as "waste." Examples of "waste generated during the manufacturing process of a water-absorbent resin" include, but are not limited to, fine powder, gel, and water-absorbent resin particles with excessively large or small particle diameters generated during the manufacturing process of a water-absorbent resin.

[0026] [1-2-4] Polyvalent metal cations The recycled water absorbent resin composition contains one or more polyvalent metal cations selected from the group consisting of calcium ions, magnesium ions, and aluminum ions. The recycled water absorbent resin composition may contain polyvalent metal cations other than calcium ions, magnesium ions, and aluminum ions.

[0027] The polyvalent metal cation in the recycled water absorbent resin composition originates from the recovered water absorbent resin and / or a compound used in the recycling process. For example, the recovered water absorbent resin contains polyvalent metal cations or polyvalent metal salts used in the manufacturing process of the water absorbent resin, or polyvalent metal cations derived from body fluids such as human waste. In addition, polyvalent metal salts may be used in the recycling process of the recovered water absorbent resin. In this case, a part of the polyvalent metal salt may be ionized to generate polyvalent metal cations, which may remain in the finally obtained recycled water absorbent resin composition.

[0028] The polyvalent metal cation in the recycled water absorbent resin composition is not particularly limited. As described above, the recycled water absorbent resin composition is derived from body fluids such as human waste and polyvalent metal salts used in the manufacturing process and recycling process, and may contain various polyvalent metal cations.

[0029] Examples of polyvalent metal cations contained in the recycled water absorbent resin composition include calcium ions, magnesium ions, and aluminum ions.

[0030] The content of the polyvalent metal cation in the recycled water absorbent resin composition is 0.001% by mass or more and 1.0% by mass or less. The lower limit of the content of the polyvalent metal cation may be 0.002% by mass or more, 0.004% by mass or more, 0.006% by mass or more, 0.008% by mass or more, or 0.01% by mass or more. The upper limit of the content of the polyvalent metal cation may be 0.90% by mass or less, 0.80% by mass or less, 0.70% by mass or less, 0.60% by mass or less, or 0.50% by mass or less. The content of the polyvalent metal cation in the recycled water absorbent resin composition can be measured by a method such as ICP emission spectrometry.

[0031] [1-2-5] Metal chelating agents The recycled water absorbent resin composition contains a metal chelating agent (excluding monovalent carboxylic acid (salt) consisting of only CHO and polyvalent carboxylic acid (salt) consisting of only CHO). By containing a metal chelating agent in the recycled water absorbent resin composition, polyvalent metal cations derived from body fluids such as human waste and / or polyvalent metal salts are captured, and the presence of polyvalent metal cations in the ionic state in the water absorbent resin composition can be reduced or prevented. As a result, the recycled water absorbent resin composition has an advantage of being excellent in water absorption performance (for example, water absorption speed) without excessive purification. In addition, by containing a metal chelating agent, the recycled water absorbent resin composition has an advantage of being excellent in one or more selected from the group consisting of color tone (for example, YI value and color), water-soluble content, and durability. In addition, by containing a metal chelating agent, the recycled water absorbent resin composition has an advantage of being almost odorless or completely odorless.

[0032] As used herein, the term "metal chelating agent" refers to a compound that has multiple reactive functional groups in one molecule that can bind to a metal contained in a polyvalent metal salt, thereby having the ability to form a complex with the metal.

[0033] Examples of reactive functional groups include carboxyl groups and phosphate groups. In a preferred embodiment, the metal chelating agent preferably has 2 or more carboxyl groups or phosphate groups in one molecule, more preferably has 3 or more, for example, 3 or more to 100 or less, more preferably has 3 or more to 20 or less, and even more preferably has 3 or more to 10 or less. In a preferred embodiment, the metal chelating agent preferably has 2 or more carboxyl groups and phosphate groups in one molecule in total, more preferably has 3 or more, for example, 3 or more to 100 or less, more preferably has 3 or more to 20 or less, and even more preferably has 3 or more to 10 or less.

[0034] Examples of metal chelating agents include monovalent carboxylic acids (salts), polyvalent carboxylic acids (salts), monovalent amino carboxylic acids (salts), amino polyvalent carboxylic acids (salts), polyphosphoric acids (salts), and organic phosphonic acids (salts). Among these, amino polyvalent carboxylic acids (salts) and polyphosphoric acids (salts) are preferred. These may be used alone or in combination of two or more.

[0035] However, in one embodiment of the present invention, the scope of the metal chelating agent excludes monovalent carboxylic acids (salts) consisting only of CHO and polyvalent carboxylic acids (salts) consisting only of CHO. Accordingly, examples of the polyvalent carboxylic acids (salts) in the metal chelating agent (A) include amino polyvalent carboxylic acids (salts), polyphosphoric acids (salts), and organic phosphonic acids (salts).

[0036] Examples of the amino polycarboxylic acid (salt) include iminodiacetic acid, hydroxyethyliminodiacetic acid, nitrilotriacetic acid, nitrilotripropionic acid, ethylenediaminetetraacetic acid, hydroxyethylenediaminetriacetic acid, hexamethylenediaminetetraacetic acid, diethylenetriaminepentaacetic acid, triethylenetetraminehexaacetic acid, trans-1,2-diaminocyclohexanetetraacetic acid, bis(2-hydroxyethyl)glycine, diaminopropanoltetraacetic acid, ethylenediamine-2-propionic acid, glycol ether diaminetetraacetic acid, bis(2-hydroxybenzyl)ethylenediaminediacetic acid, ethylenediaminedisuccinic acid, L-glutamic acid diacetic acid, 3-hydroxy-2,2'-iminodisuccinic acid, glycol ether diaminetetraacetic acid, methylglycine diacetic acid, and salts thereof.

[0037] Examples of polyphosphoric acids (salts) include pyrophosphoric acid, tripolyphosphoric acid, tetrapolyphosphoric acid, metaphosphoric acid, and salts thereof.

[0038] Examples of organic phosphonic acids (salts) include 1-hydroxyethylidene-1,1-diphosphonic acid, aminotrimethylenephosphonic acid, ethylenediaminetetra(methylenephosphonic acid), diethylenetriaminepenta(methylenephosphonic acid), etc. Examples of organic phosphonic acids (salts) that are particularly preferably used include 1-hydroxyethylidene-1,1-diphosphonic acid, ethylenediaminetetra(methylenephosphonic acid), and diethylenetriaminepenta(methylenephosphonic acid).

[0039] Specific examples of metal chelating agents include hydroxy polycarboxylic acids, amino polycarboxylic acids, organic polyphosphates, inorganic polyphosphates, amino polyphosphates, and tropolone derivatives. At least one compound selected from the group consisting of these compounds is applied in one embodiment of the present invention. The term "polyvalent" refers to having multiple functional groups in one molecule. The above-mentioned polyvalent compounds (hydroxy polycarboxylic acids, amino polycarboxylic acids, organic polyphosphates, inorganic polyphosphates, amino polyphosphates, etc.) preferably have 2 to 30 functional groups in one molecule, more preferably 3 to 20 functional groups in one molecule, and even more preferably 4 to 10 functional groups in one molecule.

[0040] From the viewpoint of the influence on polymerization and the physical properties of the resulting recycled water absorbent resin composition, the molecular weight of the metal chelating agent is preferably 100 to 5000, more preferably 200 to 1000. When the molecular weight is 5000 or less, there is no risk of the aqueous monomer solution becoming thickened regardless of the timing of adding the metal chelating agent. In other words, the molecular weight is preferably 5000 or less, since polymerization control and uniform mixing are facilitated.

[0041] Specific examples of the hydroxy polyvalent carboxylic acid include malic acid, citric acid, and salts thereof.

[0042] Specific examples of the amino polycarboxylic acid include iminodiacetic acid, hydroxyethyliminodiacetic acid, nitrilotriacetic acid, nitrilotripropionic acid, ethylenediaminetetraacetic acid, diethylenetriaminepentaacetic acid, triethylenetetraminehexaacetic acid, trans-1,2-diaminocyclohexanetetraacetic acid, N,N-bis(2-hydroxyethyl)glycine, diaminopropanoltetraacetic acid, ethylenediamine2propionic acid, N-hydroxyethylethylenediaminetriacetic acid, glycol ether diaminetetraacetic acid, diaminopropanetetraacetic acid, N,N'-bis(2-hydroxybenzyl)ethylenediamine-N,N'-diacetic acid, 1,6-hexamethylenediamine-N,N,N',N'-tetraacetic acid, and salts thereof.

[0043] Specific examples of the organic polyphosphate include nitriloacetic acid-di(methylenephosphinic acid), nitrilodiacetic acid-(methylenephosphinic acid), nitriloacetic acid-β-propionic acid-methylenephosphonic acid, nitrilotris(methylenephosphonic acid), 1-hydroxyethylidene diphosphonic acid, and salts thereof.

[0044] Specific examples of the inorganic polyphosphate include pyrophosphoric acid, tripolyphosphoric acid, and salts thereof.

[0045] Specific examples of the amino polyphosphate include ethylenediamine-N,N'-di(methylenephosphinic acid), ethylenediaminetetra(methylenephosphinic acid), cyclohexanediaminetetra(methylenephosphonic acid), ethylenediamine-N,N'-diacetic acid-N,N'-di(methylenephosphonic acid), ethylenediamine-N,N'-di(methylenephosphonic acid), ethylenediaminetetra(methylenephosphonic acid), polymethylenediaminetetra(methylenephosphonic acid), diethylenetriaminepenta(methylenephosphonic acid), and salts thereof.

[0046] Specific examples of the tropolone derivatives include tropolone, β-thujaplicin, and γ-thujaplicin.

[0047] The metal chelating agent preferably contains a polyvalent phosphoric acid (salt) and / or a polyvalent carboxylic acid (salt) having a plurality of nitrogen atoms. More specifically, the metal chelating agent preferably contains one or more selected from the group consisting of amino polyvalent carboxylic acids, organic polyvalent phosphoric acids, amino polyvalent phosphoric acids, and salts thereof, among the above-mentioned metal chelating agents, and more preferably contains only one or more selected from the group. The metal chelating agent more preferably contains one or more selected from the group consisting of amino polyvalent carboxylic acids having three or more carboxyl groups in one molecule and salts thereof, and more preferably contains only one or more selected from the group. Furthermore, from the viewpoint of gel stability, the metal chelating agent more preferably contains one or more selected from the group consisting of diethylenetriaminepentaacetic acid, triethylenetetraminehexaacetic acid, trans-1,2-diaminocyclohexanetetraacetic acid, and salts thereof, and even more preferably contains only one or more selected from the group.

[0048] When the metal chelating agent is a salt, a monovalent salt, particularly an alkali metal salt such as a sodium salt or a potassium salt, an ammonium salt, or an amine salt can be preferably used, with the sodium salt and potassium salt being particularly preferred.

[0049] The content of the metal chelating agent in the recycled water absorbent resin composition is preferably 2 times or more and 1000 times or less by mass of the content of the polyvalent metal cation in the recycled water absorbent resin composition. When the content of the metal chelating agent is 2 times or more by mass of the content of the polyvalent metal cation in the recycled water absorbent resin composition, the obtained recycled water absorbent resin composition has an advantage of being excellent in water absorption speed, and an advantage of being excellent in one or more selected from the group consisting of color tone (YI value, color, etc.), water-soluble content, and durability.

[0050] The content of the metal chelating agent in the recycled water absorbent resin composition is preferably 0.01% by mass or more and 5.0% by mass or less, in the following order, 0.01% by mass or more and 2.0% by mass or less, 0.02% by mass or more and 1.0% by mass or less, 0.03% by mass or more and 0.9% by mass or less, 0.04% by mass or more and 0.8% by mass or less, 0.05% by mass or more and 0.7% by mass or less, 0.06% by mass or more and 0.6% by mass or less, and most preferably 0.07% by mass or more and 0.5% by mass or less. When the content of the metal chelating agent is 0.01% by mass or more and 5.0% by mass or less, in the recycled water absorbent resin composition 100% by mass, the obtained recycled water absorbent resin composition has the advantage of being excellent in water absorption speed, color tone (YI value and color, etc.), water soluble content, and durability.

[0051] [1-3] Method for producing recycled water-absorbent resin composition The method for producing the present recycled water absorbent resin composition is not particularly limited, but any one of the following production methods (M1) to (M3) is preferable: (M1) A polymerization step of polymerizing a monomer constituting the water absorbent resin; and A method for producing a recycled water-absorbing resin composition, comprising a drying step of drying the polymer obtained in the polymerization step, moreover, An addition step (A) of adding a solubilized polymer derived from a water-absorbent resin recovered from used absorbent articles and / or waste generated in the manufacturing process of the water-absorbent resin; (B) adding a metal chelating agent (A) (excluding a monovalent carboxylic acid (salt) consisting of only CHO and a polyvalent carboxylic acid (salt) consisting of only CHO); (M2) A method for producing a recycled water-absorbent resin composition from a water-absorbent resin recovered from used absorbent articles and / or waste generated in a process for producing a water-absorbent resin, comprising the steps of: A washing step of washing the water absorbent resin and / or a dehydration step of dehydrating the water absorbent resin; An addition step (E) of adding a metal chelating agent (C) (excluding monovalent carboxylic acid (salt) consisting of only CHO and polyvalent carboxylic acid (salt) consisting of only CHO) to the water absorbent resin; and A drying step of drying the water absorbent resin, A method for producing a recycled water absorbent resin composition, wherein the adding step (E) is carried out after the washing step and / or the dehydrating step; (M3) In the process of producing a water-absorbent resin composition using a monomer constituting a water-absorbent resin as a raw material, A method for producing a recycled water-absorbent resin composition, comprising using, as a part of a raw material, the recycled water-absorbent resin composition obtained by the method for producing a recycled water-absorbent resin composition of (M2) above.

[0052] The above-mentioned methods for producing recycled water absorbent resin compositions (M1) to (M3) are also referred to as "production method (M1)", "production method (M2)" and "production method (M3)", respectively. Hereinafter, the production method (M1), the production method (M2) and the production method (M3) will be described respectively.

[0053] [1-3-1] Manufacturing method (M1) [1-3-1-1] Polymerization process In the polymerization step, a polymer can be obtained by polymerizing the monomers constituting the water absorbent resin. In the polymerization step, as an example, a polymer can be obtained by carrying out a polymerization reaction using an aqueous solution (monomer aqueous solution) containing the monomers constituting the water absorbent resin. In other words, a polymer can be obtained by polymerizing the monomers in the monomer aqueous solution. In the production method (M1), a monomer slurry liquid can be used in addition to the monomer aqueous solution within a range in which the water absorption performance of the obtained water absorbent resin is not reduced, but for the sake of convenience, the case of using a monomer aqueous solution will be described in this section.

[0054] The polymerization step may include a step of preparing an aqueous monomer solution for use in the polymerization step.

[0055] (Preparation of Monomer Aqueous Solution) The aqueous monomer solution is preferably an aqueous solution containing acrylic acid (salt) as a main component.

[0056] The above-mentioned "main component" means that the amount (content) of acrylic acid (salt) used is 50 mol% or more in the total amount (100 mol%) of monomers (in other words, monomers contained in the aqueous monomer solution, excluding the internal crosslinking agent) to be subjected to the polymerization reaction of the water absorbent resin. The content of acrylic acid (salt) in the total amount (100 mol%) of monomers is preferably 70 mol% or more, more preferably 90 mol% or more (upper limit: 100 mol%).

[0057] (acrylic acid) As a monomer serving as a raw material for the water absorbent resin in the production method (M1), acrylic acid and / or a salt thereof (hereinafter referred to as "acrylic acid (salt)") is used from the viewpoints of the physical properties and productivity of the resulting water absorbent resin.

[0058] The term "acrylate" refers to acrylic acid neutralized with a basic composition. The acrylate may be a commercially available acrylate (e.g., sodium acrylate) or may be one obtained by neutralization in a water absorbent resin manufacturing plant.

[0059] (Basic Composition) In the present specification, the term "basic composition" refers to a composition containing a basic compound. More specifically, the basic compound may be an alkali metal carbonate and / or hydrogen carbonate, an alkali metal hydroxide, ammonia, an organic amine, or the like. Among these, from the viewpoint of the physical properties of the obtained water absorbent resin, a strongly basic basic compound, for example, an alkali metal hydroxide such as sodium hydroxide, potassium hydroxide, or lithium hydroxide, is preferred, and sodium hydroxide is more preferred.

[0060] (neutralization) In the production method (M1), it is preferable to neutralize at least a part of the acrylic acid. As the neutralization in the production method (M1), either neutralization of the acrylic acid (before polymerization) or neutralization of the polymer (e.g., hydrogel-like crosslinked polymer) obtained by polymerizing the acrylic acid (after polymerization) (hereinafter referred to as "post-neutralization") can be selected or used in combination. In addition, the mode of these neutralizations is not particularly limited, and may be continuous or batchwise, but continuous is preferable from the viewpoint of production efficiency, etc.

[0061] Regarding the conditions such as the neutralization device, neutralization temperature, and residence time, the conditions described in International Publication No. 2009 / 123197 and U.S. Patent Application Publication No. 2008 / 0194863 may be applied to one embodiment of the present invention.

[0062] The neutralization rate of the monomer (monomer having an acid group including acrylic acid) in the production method (M1) is preferably 10 mol% or more and 90 mol% or less, more preferably 40 mol% or more and 85 mol% or less, further preferably 50 mol% or more and 80 mol% or less, and particularly preferably 60 mol% or more and 75 mol% or less, based on the total amount of the acid groups of the monomer (100 mol%). By setting the neutralization rate to 10 mol% or more, a water absorbent resin having a sufficient water absorption capacity can be provided, and by setting the neutralization rate to 90 mol% or less, a water absorbent resin having a higher water absorption capacity under pressure can be provided. The neutralization rate of the aqueous monomer solution will be further described by taking as an example a case where the aqueous monomer solution contains only acrylic acid as a monomer component. In this case, the neutralization rate of the monomer is 75 mol% means that the monomer component contained in the aqueous monomer solution is a mixture of 25 mol% acrylic acid and 75 mol% acrylic acid salt. Such a mixture may be called a partially neutralized product of acrylic acid.

[0063] The above neutralization rate is the same in the case of post-neutralization. The above neutralization rate is also applied to the neutralization rate of the water absorbent resin as a final product. In the production method (M1), as described later, the solubilized polymer of the recovered water absorbent resin is used as a part of the raw material for producing the water absorbent resin. There is a possibility that the solubilized polymer derived from such a recovered water-absorbing resin contains a basic compound. Therefore, when the solubilized polymer of the recovered water-absorbing resin is used as a part of the raw material for producing a water-absorbing resin, the basic compound contained in the solubilized polymer may neutralize the acrylic acid before polymerization or the polymer after polymerization (for example, the hydrogel-like cross-linked polymer). Therefore, taking into account the neutralization by the basic compound derived from the solubilized polymer, the neutralization (post-neutralization) rate of the monomer in the aqueous monomer solution, the polymer after polymerization, and the water-absorbing resin as the final product is adjusted to a predetermined range.

[0064] (Other monomers) The aqueous monomer solution may contain a monomer (other monomer) other than the acrylic acid (salt). In the production method (M1), such other monomer can be used in combination with the acrylic acid (salt) to produce a water-absorbing resin.

[0065] The other monomer may be a water-soluble or hydrophobic unsaturated monomer. Specifically, anionic unsaturated monomers such as (anhydrous) maleic acid, fumaric acid, crotonic acid, itaconic acid, cinnamic acid, vinyl sulfonic acid, allyl toluene sulfonic acid, vinyl toluene sulfonic acid, styrene sulfonic acid, 2-(meth)acrylamido-2-methylpropanesulfonic acid, 2-(meth)acryloylethanesulfonic acid, 2-(meth)acryloylpropanesulfonic acid, and 2-hydroxyethyl (meth)acryloyl phosphate and / or salts thereof may be suitably used as the other monomer. Moreover, these other monomers may be used alone or in combination of two or more.

[0066] (Internal crosslinking agent) The aqueous monomer solution preferably contains an internal crosslinking agent. As the internal crosslinking agent that can be contained in the aqueous monomer solution, for example, the compounds described in U.S. Patent No. 6,241,928 can be mentioned. Among these, one or more compounds can be used as the internal crosslinking agent in consideration of reactivity.

[0067] When the polymerization step is carried out using an aqueous monomer solution that contains an internal crosslinking agent, the resulting polymer may be internally crosslinked and may therefore also be referred to as a "crosslinked polymer."

[0068] In addition, from the viewpoint of the water absorption performance of the obtained water absorbent resin, the internal crosslinking agent is preferably a compound having two or more polymerizable unsaturated groups, more preferably a compound having thermal decomposition properties at the drying temperature described below, and further preferably a compound having two or more polymerizable unsaturated groups having a (poly)alkylene glycol structural unit.

[0069] The polymerizable unsaturated group is preferably, for example, an allyl group or a (meth)acrylate group, more preferably a (meth)acrylate group. The (poly)alkylene glycol structural unit is preferably polyethylene glycol, and the number n is preferably 1 or more and 100 or less, more preferably 6 or more and 50 or less.

[0070] The amount of the internal crosslinking agent used (content in the aqueous monomer solution) is preferably 0.0001 mol% or more and 10 mol% or less, more preferably 0.001 mol% or more and 1 mol% or less, based on the total amount of the monomer. By setting the amount of the internal crosslinking agent used within the above range, a water-absorbing resin having a desired water-absorbing performance can be obtained. If the amount of the internal crosslinking agent used is less than 0.0001 mol%, the gel strength of the obtained water-absorbing resin tends to decrease and the water-soluble content tends to increase excessively, and if the amount of the internal crosslinking agent used is more than 10 mol%, the water absorption capacity of the obtained water-absorbing resin tends to decrease, which is not preferable. The mol% relative to the total monomer is the percentage of the number of moles of the internal crosslinking agent relative to the total number of moles of the monomer contained in the aqueous monomer solution.

[0071] In the manufacturing method (M1), a method is preferably applied in which a predetermined amount (within the above range) of an internal crosslinking agent is added to the monomer aqueous solution in advance, and the crosslinking reaction is started simultaneously with the polymerization. On the other hand, in addition to this method, a method of post-crosslinking by adding an internal crosslinking agent during and / or after polymerization; a method of radical crosslinking using a radical polymerization initiator; a method of radiation crosslinking using active energy rays such as electron beams and ultraviolet rays, etc. can also be adopted. These methods can also be used in combination.

[0072] (Polymerization inhibitor) From the viewpoint of the polymerizability of acrylic acid and the color tone of the water-absorbing resin, the aqueous monomer solution preferably contains a polymerization inhibitor in an amount of 200 ppm or less, more preferably 10 ppm or more and 160 ppm or less, and even more preferably 20 ppm or more and 100 ppm or less. The polymerization inhibitor is not particularly limited, but is preferably a methoxyphenol, more preferably p-methoxyphenol.

[0073] In addition, the recovered water absorbent resin may contain a polymerization inhibitor (e.g., p-methoxyphenol) depending on the manufacturing process of the water absorbent resin from which it is derived. In that case, the solubilized polymer obtained from the recovered water absorbent resin may also contain a polymerization inhibitor (e.g., p-methoxyphenol). In other words, in the manufacturing method (M1), the solubilized polymer described later may contain p-methoxyphenol.

[0074] The aqueous monomer solution according to the production method (M1) may contain impurities derived from each component in the aqueous monomer solution. For example, the description of the compounds described in U.S. Patent Application Publication No. 2008 / 0161512 regarding impurities derived from acrylic acid may be applied to one embodiment of the present invention.

[0075] (Other substances) The aqueous monomer solution may contain substances (other substances) other than the above-mentioned components from the viewpoint of improving the physical properties of the resulting water-absorbing resin.

[0076] Examples of other substances include hydrophilic polymers such as starch, starch derivatives, cellulose, cellulose derivatives, polyvinyl alcohol, polyacrylic acid (salts), and crosslinked polyacrylic acid (salts); and other additives such as foaming agents such as carbonates and azo compounds, surfactants, chelating agents, and chain transfer agents.

[0077] When the aqueous monomer solution contains a hydrophilic polymer as an additional substance, the content of the hydrophilic polymer is preferably 50% by mass or less, more preferably 20% by mass or less, even more preferably 10% by mass or less, and particularly preferably 5% by mass or less (the lower limit is 0% by mass) relative to the total amount (100% by mass) of the aqueous monomer solution. When the aqueous monomer solution contains other additives as additional substances, the content of the other additives is preferably 5% by mass or less, more preferably 1% by mass or less, and even more preferably 0.5% by mass or less (the lower limit is 0% by mass) relative to the total amount (100% by mass) of the aqueous monomer solution.

[0078] The above-mentioned other substances may be added to the reaction system after the initiation of polymerization. In this case, it is preferable that the total amount of the other substances contained in the aqueous monomer solution and the other substances added to the reaction system after the initiation of polymerization is within the above-mentioned range.

[0079] When a water-soluble resin or a water-absorbent resin is used as the hydrophilic polymer, a graft polymer or a water-absorbent resin composition (e.g., a starch-acrylic acid polymer, a PVA-acrylic acid polymer, etc.) is obtained. These polymers and water-absorbent resin compositions also fall within the scope of one embodiment of the present invention.

[0080] (Polymerization initiator) In the polymerization step, it is preferable to carry out a polymerization reaction of the monomer using a polymerization initiator. The polymerization initiator used in the polymerization step is appropriately selected depending on the polymerization form and the like, and is not particularly limited. For example, a thermal decomposition type polymerization initiator, a photodecomposition type polymerization initiator, or a redox type polymerization initiator used in combination with a reducing agent that promotes the decomposition of these polymerization initiators can be mentioned. Specifically, one or more of the polymerization initiators disclosed in U.S. Pat. No. 7,265,190 can be suitably used. In addition, from the viewpoint of handling and the physical properties of the obtained water-absorbing resin, the polymerization initiator is preferably a peroxide or an azo compound, more preferably a peroxide, and even more preferably a persulfate.

[0081] The amount of the polymerization initiator used in the polymerization step is preferably 0.001 mol% or more and 1 mol% or less, more preferably 0.001 mol% or more and 0.5 mol% or less, based on the total amount of the monomers to be polymerized (monomers contained in the aqueous monomer solution). When a reducing agent is used in combination (i.e., when a redox polymerization initiator is used), the amount of the reducing agent used is preferably 0.0001 mol% or more and 0.02 mol% or less, based on the total amount of the monomers. The mol% relative to the monomer refers to the percentage of the number of moles of the polymerization initiator or reducing agent relative to the total number of moles of the monomers contained in the aqueous monomer solution.

[0082] In addition, instead of the above polymerization initiator, the polymerization reaction may be carried out by irradiation with active energy rays such as radiation, electron beams, and ultraviolet rays, or the polymerization reaction may be carried out by using these active energy rays in combination with the polymerization initiator.

[0083] (polymerization form) The polymerization form in the polymerization step is not particularly limited, but from the viewpoint of the water absorption properties of the obtained water absorbent resin and the ease of polymerization control, etc., preferably, spray droplet polymerization, aqueous solution polymerization, reversed phase suspension polymerization, more preferably aqueous solution polymerization, reversed phase suspension polymerization, and further preferably aqueous solution polymerization are mentioned. Among them, continuous aqueous solution polymerization is particularly preferable. Forms such as continuous belt polymerization and continuous kneader polymerization can also be applied. In addition, a foaming polymerization form in which bubbles (particularly inert gas, etc.) are dispersed in a monomer aqueous solution to carry out polymerization can also be applied.

[0084] As specific polymerization forms, continuous belt polymerization is disclosed in U.S. Patent Nos. 4,893,999, 6,241,928, U.S. Patent Application Publication No. 2005 / 215734, etc., and continuous kneader polymerization is disclosed in U.S. Patent Nos. 6,987,151, 6,710,141, etc. By adopting these continuous aqueous solution polymerizations, the production efficiency of the water absorbent resin can be improved.

[0085] The polymerization form may also be acid polymerization. Acid polymerization is a method of obtaining a polymer by polymerizing an acid group-containing monomer including unneutralized acrylic acid and then neutralizing it with a basic composition. A specific embodiment of acid polymerization is disclosed in JP-A-1-103606.

[0086] In addition, preferred forms of the continuous aqueous solution polymerization include "high-temperature initiated polymerization" and "high-concentration polymerization." "High-temperature initiated polymerization" refers to a form in which polymerization is initiated at a temperature of preferably 30°C or higher, more preferably 35°C or higher, even more preferably 40°C or higher, and particularly preferably 50°C or higher (upper limit is the boiling point). "High-concentration polymerization" refers to a form in which polymerization is performed at a monomer concentration of preferably 30% by mass or higher, more preferably 35% by mass or higher, even more preferably 40% by mass or higher, and particularly preferably 45% by mass or higher (upper limit is the saturated concentration). These polymerization forms can also be used in combination.

[0087] In the polymerization step, the polymerization can be carried out under a desired atmosphere, for example, under an air atmosphere, but from the viewpoint of the color tone of the obtained water absorbent resin, it is preferable to carry out the polymerization under an inert gas atmosphere such as nitrogen or argon. In this case, it is preferable to control the oxygen concentration to 1 volume % or less. It is also preferable to replace the dissolved oxygen in the aqueous monomer solution with an inert gas (for example, to make the dissolved oxygen less than 1 mg / l).

[0088] In one embodiment of the present invention, the polymerization may be carried out as foaming polymerization in which bubbles (particularly the above-mentioned inert gases or the like) are dispersed in an aqueous monomer solution.

[0089] When the polymerization form in the polymerization step is aqueous solution polymerization, that is, when the monomer is polymerized in an aqueous solution state, the obtained polymer may be in a gel state containing water. Therefore, when such a polymerization form is adopted, the polymer obtained in the polymerization step may be called a "water-containing gel," "gel," "water-containing gel-like polymer," or "gel-like polymer."

[0090] In the polymerization step, an oxidizing agent may be added to the system. In this specification, the oxidizing agent added to the system in the polymerization step is also referred to as oxidizing agent (B) for convenience. Specific examples of the oxidizing agent in the oxidizing agent (B) are the same as the specific examples of the oxidizing agent as a decomposition agent described in detail in the section ([1-3-1-8] Solubilization step) described later, so the description is incorporated herein and will not be repeated here.

[0091] [1-3-1-2] Drying process The production method (M1) includes a drying step in which the polymer (e.g., hydrogel) obtained in the polymerization step is dried. In the drying step, for example, the polymer obtained in the polymerization step is dried to a desired resin solid content to obtain a dried polymer. The resin solid content of the dried polymer is determined from the loss on drying (the change in mass when 1 g of the dried polymer is heated at 180°C for 3 hours), and is preferably 80% by mass or more, more preferably 85% by mass to 99% by mass, even more preferably 90% by mass to 98% by mass, and particularly preferably 92% by mass to 97% by mass.

[0092] The method for drying the polymer is not particularly limited, and examples thereof include heat drying, hot air drying, reduced pressure drying, fluidized bed drying, infrared drying, microwave drying, drum dryer drying, drying by azeotropic dehydration with a hydrophobic organic solvent, superheated steam drying using high-temperature steam, etc. Among these, from the viewpoint of drying efficiency, hot air drying is preferred, and band drying in which hot air drying is performed on a ventilation belt is more preferred.

[0093] The drying temperature (hot air temperature) in the hot air drying is preferably 120°C or higher and 250°C or lower, more preferably 150°C or higher and 200°C or lower, from the viewpoint of the color tone and drying efficiency of the obtained water-absorbent resin. The drying conditions other than the drying temperature, such as the hot air speed and drying time, can be appropriately set according to the water content and total mass of the polymer to be dried and the target resin solid content. In addition, when band drying is performed, the various conditions described in International Publication Nos. 2006 / 100300, 2011 / 025012, 2011 / 025013, 2011 / 111657, etc. are appropriately applied as drying conditions.

[0094] [1-3-1-3] Addition step (A) The manufacturing method (M1) includes an addition step (A) of adding a solubilized polymer derived from a water-absorbent resin recovered from a used absorbent article and / or a solubilized polymer derived from a water-absorbent resin recovered from waste generated in the manufacturing process of the water-absorbent resin, for example, to a reaction system. By adding the solubilized polymer to the reaction system, the solubilized polymer can be used as a part of the raw material. Therefore, in other words, the addition step (A) can be said to be a step of adding a solubilized polymer derived from a water-absorbent resin recovered from a used absorbent article or waste generated in the manufacturing process of the water-absorbent resin, to the system as a part of the raw material.

[0095] In the actual collection of used absorbent articles, used sanitary materials of various types and manufacturers can be collected without distinction between types and manufacturers. In addition, various types of water absorbent resins are manufactured by various manufacturers, and water absorbent resins can be collected from waste generated in the manufacturing process of each of these manufacturers without distinction between types and manufacturers. Therefore, the recovered water absorbent resins may include used water absorbent resins of various manufacturers and various types. That is, in the manufacturing method (M1), the water absorbent resin (recovered water absorbent resin) may be a water absorbent resin recovered from one or more types of used absorbent articles and / or one or more types of waste generated in the manufacturing process of one or more types of water absorbent resins, and the solubilized polymer may be a solubilized polymer derived from a water absorbent resin recovered from one or more types of used absorbent articles and / or one or more types of waste generated in the manufacturing process of one or more types of water absorbent resins. In other words, the obtained recycled water absorbent resin composition may contain multiple types of water absorbent resins.

[0096] In the past, when recycled water absorbent resins containing various kinds of water absorbent resins from various manufacturers were used as a part of the raw material to obtain a recycled water absorbent resin composition, the water absorption performance of the obtained recycled water absorbent resin composition was not stable in some cases. However, the manufacturing method (M1) has an advantage that a recycled water absorbent resin composition having excellent water absorption speed can be obtained even when a solubilized polymer derived from recycled water absorbent resins containing various kinds of water absorbent resins from various manufacturers is used.

[0097] The method of adding the solubilized polymer to the reaction system includes, but is not limited to, adding it as an aqueous solution, adding it as a powder after drying once, and adding it in a slurry state with some undissolved matter remaining. From the viewpoint of the mixability of the solubilized polymer and the aqueous monomer solution, the adding step (A) is preferably a step of adding the solubilized polymer in the form of an aqueous solution at 30°C or higher. The temperature of the aqueous solution of the solubilized polymer is more preferably 40°C or higher, and even more preferably 50°C or higher.

[0098] In addition, the solubilized polymer may contain a basic compound derived from the recovered water absorbent resin as a raw material. When the solubilized polymer derived from the recovered water absorbent resin contains a basic compound, the neutralization rate of the monomer and / or the water absorbent resin as a final product may change by adding the solubilized polymer to the raw material of the water absorbent resin (e.g., a monomer aqueous solution). Therefore, when the solubilized polymer derived from the recovered water absorbent resin is added to the raw material of the water absorbent resin, it is preferable to adjust the neutralization rate of the monomer and the neutralization rate of the water absorbent resin as a final product to fall within a predetermined range, taking into account the amount of the basic compound contained in the solubilized polymer.

[0099] In the manufacturing method (M1), the timing of carrying out the addition step (A), i.e., the timing of adding the solubilizing polymer, is not particularly limited. The addition step (A) is preferably carried out, for example, before any of the above-mentioned polymerization step and drying step, and the below-mentioned addition step (B), pulverization step, classification step, and surface crosslinking step, during any of the steps, or after any of the steps. In other words, the solubilizing polymer is preferably added to the reaction system, for example, before any of the above-mentioned polymerization step and drying step, and the below-mentioned addition step (B), pulverization step, classification step, and surface crosslinking step, during any of the steps, or after any of the steps.

[0100] It is preferable that the addition step (A) is performed during the polymerization step (between the polymerization steps). When the addition step (A) is performed during the polymerization step, the addition step (A) may be performed during the preparation step of the aqueous monomer solution. When the addition step (A) is performed during the preparation step of the aqueous monomer solution, the solubilized polymer may be added to the aqueous monomer solution, or the solubilized polymer may be mixed in advance with water and then mixed with other raw materials. Among these, it is preferable to add the solubilized polymer to the aqueous monomer solution from the viewpoint of uniform mixing of the raw materials. When the addition step (A) is performed during the polymerization step, in another embodiment, the solubilized polymer may be added to the reaction system before the start of polymerization, or may be added to the reaction system after the start of polymerization. Among these, it is preferable to add the solubilized polymer to the reaction system before the start of polymerization from the viewpoint of uniformity of the polymer component.

[0101] When the addition step (A) is carried out during the drying step, the polymer (e.g., a hydrogel) and the solubilized polymer may be mixed before drying, or the polymer and the solubilized polymer may be mixed after drying.

[0102] When the addition step (A) is carried out during the addition step (B) described later (simultaneously with the addition step (B)), the solubilizing polymer and the metal chelating agent (A) may be added together to the reaction system. For example, the solubilizing polymer and the metal chelating agent (A) may be mixed, and then the resulting mixture may be added to the reaction system.

[0103] When the addition step (A) is carried out during the grinding step described below, the solubilizing polymer may be added to the reaction system before grinding, or may be added to the reaction system during grinding. Furthermore, the solubilizing polymer may be added to the reaction system in portions. From the viewpoint of uniformity of the gel component, it is preferable to add the solubilizing polymer to the reaction system before gel grinding.

[0104] When the addition step (A) is carried out during the classification step described below, the polymer (e.g., a dried polymer) and the solubilized polymer may be mixed before classification, or the polymer and the solubilized polymer may be mixed after classification. From the viewpoint of uniformity of particle size, it is preferable to add the solubilized polymer to the polymer before classification.

[0105] When the addition step (A) is carried out during the surface cross-linking step described later, the water absorbent resin dried in advance may be mixed with the solubilized polymer, or the water absorbent resin surface-cross-linked after surface cross-linking may be mixed with the solubilized polymer. From the viewpoint of uniform mixing of the surface cross-linking liquid and the water absorbent resin, it is preferable to use a powdery solubilized polymer and subject all the surface-cross-linked materials (i.e., particulate dried polymer and powdery solubilized polymer) to surface cross-linking in the form of powder. In addition, when the solubilized polymer is mixed after surface cross-linking, it is preferable to use a solubilized polymer derived from the surface-cross-linked recovered water absorbent resin as the solubilized polymer.

[0106] The solubilized polymer can be obtained by decomposing the recovered water absorbent resin. For example, the method of decomposing the recovered water absorbent resin includes the solubilization step described later. The solubilized polymer may contain a decomposing agent and / or an oxidizing agent used in the process of decomposing the recovered water absorbent resin. The decomposing agent and the oxidizing agent will be described in detail in the section on the solubilization step described later.

[0107] The recovered water absorbent resin may contain a metal chelating agent because the metal chelating agent was used in the manufacturing process of the water absorbent resin before the use of the recovered water absorbent resin. As a result, the solubilized polymer derived from the recovered water absorbent resin may also contain a metal chelating agent (B). In this specification, the metal chelating agent contained in the recovered water absorbent resin and the metal chelating agent contained in the solubilized polymer are also referred to as the metal chelating agent (B) for convenience.

[0108] The content of the metal chelating agent (B) contained in the solubilized polymer is not particularly limited, but is preferably 0.00001% by mass or more and 5% by mass or less, more preferably 0.0005% by mass or more and 2% by mass or less, and even more preferably 0.0001% by mass or more and 1% by mass or less, in 100% by mass of the solubilized polymer. When the content of the metal chelating agent (B) in 100% by mass of the solubilized polymer is within the above range, the recycled water absorbent resin composition has an advantage of being excellent in water absorption properties (especially water absorption speed). The amount of the metal chelating agent in the solubilized polymer can be measured by liquid chromatography.

[0109] Specific examples of the metal chelating agent (B) are the same as those explained in the section "(1-2-5) Metal chelating agents" above, so the explanation therein is incorporated by reference and will not be repeated here.

[0110] The molecular weight of the solubilizing polymer used in the addition step (A) is preferably as low as possible from the viewpoints of handling of the solubilizing polymer aqueous solution and mixability with other raw materials, but is preferably as high as possible from the viewpoints of the balance of water absorption properties of the water absorbent resin, reduction of soluble content, etc. Therefore, from the viewpoints of obtaining a solubilizing polymer with a good balance between mixability with other raw materials and water absorption properties and reduced soluble content, the mass average molecular weight of the solubilizing polymer is preferably from 30,000 to 1,000,000, and more preferably from 40,000 to 800,000.

[0111] The amount of the solubilizing polymer used (addition amount) in the addition step (A) is not particularly limited, but for example, is preferably 1 mass % or more and 60 mass % or less, more preferably 3 mass % or more and 50 mass % or less, and even more preferably 5 mass % or more and 40 mass % or less, based on the total amount of the recycled water absorbent resin composition.

[0112] In the production method (M1), the adding step (A) needs to be carried out at least once, but may be carried out multiple times.

[0113] [1-3-1-4] Addition step (B) In this specification, the metal chelating agent used in the addition step (B) is referred to as metal chelating agent (A) for the sake of convenience.

[0114] The manufacturing method (M1) includes an addition step (B) of adding a metal chelating agent (A) to, for example, a reaction system. By adding the metal chelating agent (A) to the reaction system, when the recovered water absorbent resin contains polyvalent metals derived from sewage, the metal chelating agent (A) can be captured, and the presence of the polyvalent metals in an ionic state in the obtained recycled water absorbent resin composition can be reduced or prevented. As a result, the obtained recycled water absorbent resin composition has an advantage of being excellent in water absorption performance (for example, water absorption speed) without excessive purification.

[0115] Specific examples of the metal chelating agent (A) are the same as those explained in the section "(1-2-5) Metal chelating agents" above, so the explanation therein is incorporated by reference and will not be repeated here.

[0116] Examples of the method for adding the metal chelating agent (A) to the reaction system include, but are not limited to, a method in which the metal chelating agent (A) is added as is, a method in which the metal chelating agent (A) is added in the form of a solution or a slurry, and the like.

[0117] In the manufacturing method (M1), the timing of carrying out the addition step (B), i.e., the timing of adding the metal chelating agent (A), is not particularly limited. The addition step (B) is preferably carried out, for example, before any of the above-mentioned polymerization step, drying step, and addition step (A), as well as the below-mentioned pulverization step, classification step, and surface crosslinking step, during any of the steps, or after any of the steps. In other words, the metal chelating agent (A) is preferably added to the reaction system, for example, before any of the above-mentioned polymerization step, drying step, and addition step (A), as well as the below-mentioned pulverization step, classification step, and surface crosslinking step, during any of the steps, or after any of the steps.

[0118] It is preferable that the addition step (B) is carried out during the polymerization step. When the addition step (B) is carried out during the polymerization step, the addition step (B) may be carried out during the preparation step of the aqueous monomer solution. When the addition step (B) is carried out during the preparation step of the aqueous monomer solution, the metal chelating agent (A) may be added to the aqueous monomer solution, or the metal chelating agent (A) may be mixed in advance with water and then mixed with other raw materials. When the addition step (A) is carried out during the polymerization step, in another embodiment, the metal chelating agent (A) may be added to the reaction system before the start of polymerization, or may be added to the reaction system after the start of polymerization. Among these, from the viewpoint of the mixability of the metal chelating agent and the aqueous monomer solution, it is preferable to add the metal chelating agent (A) to the reaction system before the start of polymerization. Furthermore, it is particularly preferable that the addition step (B) of adding the metal chelating agent (A) is carried out simultaneously with the addition step (A) of adding the solubilizing polymer. In this case, the solubilizing polymer and the metal chelating agent (A) may be added together to the aqueous monomer solution, or the solubilizing polymer and the metal chelating agent (A) may be mixed together and then the resulting mixture may be added to the aqueous monomer solution.

[0119] The addition step (B) may be performed after the drying step. When the addition step (B) is performed after the drying step, (i) the metal chelating agent (A) may be added directly to the water absorbent resin after drying (recycled water absorbent resin) and then mixed, or (ii) an aqueous solution of the metal chelating agent (A) may be added to the water absorbent resin after drying (recycled water absorbent resin), and then these may be mixed, and then the obtained water absorbent resin may be dried again.

[0120] The amount (addition amount) of the metal chelating agent (A) used in the addition step (B) is not particularly limited, but for example, it is preferably 0.01% by mass or more and 5.0% by mass or less with respect to 100% by mass of the finally obtained recycled water absorbent resin composition, and in the following order, it is preferably 0.01% by mass or more and 2.0% by mass or less, 0.02% by mass or more and 1.0% by mass or less, 0.03% by mass or more and 0.9% by mass or less, 0.04% by mass or more and 0.8% by mass or less, 0.05% by mass or more and 0.7% by mass or less, 0.06% by mass or more and 0.6% by mass or less, and most preferably 0.07% by mass or more and 0.5% by mass or less. When the amount of the metal chelating agent (A) used is 0.01% by mass or more and 5.0% by mass or less with respect to 100% by mass of the recycled water absorbent resin composition, the obtained recycled water absorbent resin composition has an advantage that the water absorption performance (for example, water absorption speed) is more excellent.

[0121] The recovered water absorbent resin, which is the raw material of the solubilized polymer, may contain one or more polyvalent metal cations selected from the group consisting of polyvalent metal cations, such as calcium ions, magnesium ions, and aluminum ions. Therefore, the solubilized polymer (or the solubilized polymer aqueous solution) may also contain one or more polyvalent metal cations, such as calcium ions, magnesium ions, and aluminum ions. One of the purposes of adding the metal chelating agent (A) is to capture the polyvalent metal cations. Therefore, it is preferable that the amount of the metal chelating agent (A) used (added amount) in the addition step (B) is appropriately set according to the total mass of the polyvalent metal cations brought into the system from the solubilized polymer added in the addition step (A). The amount (addition amount) of the metal chelating agent (A) used in the addition step (B) is, for example, preferably 2 times or more and 1000 times or less in mass relative to the total mass of the polyvalent metal cations brought into the system from the solubilized polymer, more preferably 2.5 times or more and 500 times or less in mass, and even more preferably 3 times or more and 100 times or less in mass. When the amount of the metal chelating agent (A) used is 2 times or more and 1000 times or less in mass relative to the total mass of the polyvalent metal cations brought into the system from the solubilized polymer, the obtained recycled resin has an advantage of being more excellent in water absorption performance (for example, water absorption speed). The amount of polyvalent metal cations in the solubilized polymer can be measured by a method such as ICP emission spectroscopy.

[0122] In the manufacturing method (M1), the addition step (B) may be carried out at least once, but may be carried out multiple times. In the manufacturing method (M1), when the addition step (B) is carried out multiple times, it is preferable that the addition step (B) is carried out during the polymerization step, and is carried out again after the drying step (i.e., it is carried out a total of two times). In a more preferred embodiment of the manufacturing method (M1), both the addition step (A) and the addition step (B) are carried out during the polymerization step, and the addition step (B) is carried out again after the drying step.

[0123] [1-3-1-5] Addition step (C) It is preferable that the production method (M1) further comprises, after the polymerization step, an addition step (C) of adding an inorganic reducing agent, for example, to the reaction system.

[0124] The inorganic reducing agent is not particularly limited, but for example, a sulfur-based inorganic reducing agent is preferable, and examples thereof include sodium sulfite, potassium sulfite, calcium sulfite, ammonium sulfite, sulfurous acid, sodium hydrogen sulfite, potassium hydrogen sulfite, ammonium hydrogen sulfite, sodium thiosulfate, potassium thiosulfate, ammonium thiosulfate, and magnesium thiosulfate. One or more of these may be used. Among these, sulfites and hydrogen sulfites are preferable in terms of effect and cost.

[0125] Examples of the method for adding the inorganic reducing agent to the reaction system include, but are not limited to, a method in which the inorganic reducing agent is added as is, a method in which the inorganic reducing agent is added in the form of a solution or a slurry, and the like.

[0126] The amount of inorganic reducing agent used (addition amount) in the addition step (C) is not particularly limited, but is preferably 0.05 parts by mass or more and 10 parts by mass or less, and more preferably 0.1 parts by mass or more and 8 parts by mass or less, relative to 100 parts by mass of the water absorbent resin. When the amount of inorganic reducing agent used in the addition step (C) is 0.05 parts by mass or more relative to 100 parts by mass of the water absorbent resin, it has the advantage that the residual monomer reduction effect can be sufficiently obtained. When the amount of inorganic reducing agent used in the addition step (C) is 10 parts by mass or less relative to 100 parts by mass of the water absorbent resin, it is an appropriate amount to be added for the required residual monomer reduction effect, there is no risk of deterioration of physical properties, and it is also advantageous in terms of cost.

[0127] [1-3-1-6] Addition step (D) It is preferable that the production method (M1) further comprises, after the drying step, an addition step (D) of adding inorganic particles, for example, to the reaction system.

[0128] Examples of inorganic particles include, but are not limited to, metal oxides such as silicon dioxide, titanium oxide, zinc oxide, and aluminum oxide; silicic acid (salts) such as calcium phosphate, natural zeolite, and synthetic zeolite; kaolin, talc, clay, bentonite, and hydrotalcite.

[0129] As the inorganic particles, inorganic fine particles having a volume average particle diameter of 200 μm or less as measured by the Coulter counter method are preferable, and inorganic fine particles having a volume average particle diameter of 20 μm or less are more preferable, and silicon dioxide or silicic acid (salt) having a volume average particle diameter of 200 μm or less (more preferably 20 μm or less) is particularly preferable.

[0130] Examples of methods for adding inorganic particles to a reaction system include, but are not limited to, a method in which the inorganic particles are added as they are, a method in which the inorganic particles are added in the form of a solution or a slurry, and the like.

[0131] In the manufacturing method (M1), the timing of carrying out the adding step (D), i.e., the timing of adding inorganic particles, is not particularly limited as long as it is after the drying step.The adding step (D) is preferably carried out, for example, before any of the classification step and the surface cross-linking step described below, during any of the steps, or after any of the steps.In other words, it is preferable that the inorganic particles are added to the reaction system, for example, before any of the classification step and the surface cross-linking step described below, during any of the steps, or after any of the steps.

[0132] The amount of inorganic particles used (addition amount) in the addition step (D) is not particularly limited, but is preferably 0.05% by mass or more and 1.0% by mass or less, more preferably 0.05% by mass or more and 0.8% by mass or less, further preferably 0.05% by mass or more and 0.7% by mass or less, and particularly preferably 0.1% by mass or more and 0.5% by mass or less, based on the total amount of the recycled water absorbent resin composition. When the amount of inorganic particles used in the addition step (D) is within the above range based on the total amount of the recycled water absorbent resin composition, it has the advantage of being more excellent in water absorption performance (for example, water absorption speed).

[0133] [1-3-1-7] Solubilization process The manufacturing method (M1) preferably includes a solubilization step of solubilizing the recovered water absorbent resin to obtain a solubilized polymer. The solubilization step can also be said to be a step of solubilizing the recovered water absorbent resin in water to obtain a solubilized polymer. The solubilized polymer obtained in the solubilization step may be entirely solubilized in water, or may be a partially solubilized product containing a polymer that is not partially solubilized.

[0134] The method for solubilizing the recovered water absorbent resin is not particularly limited as long as it can decompose the recovered water absorbent resin and solubilize it in water. For example, a method for decomposing and solubilizing the recovered water absorbent resin with a decomposing agent (e.g., a reducing agent and a transition metal ion, etc.) (e.g., the method described in JP 2019-131789 A) can be mentioned.

[0135] Another example of a method using a decomposition agent is a method in which the recovered water absorbent resin is solubilized using ascorbic acid, a reducing agent, under conditions of pH 4 to 7.5 (for example, the method described in Japanese Patent No. 3146053).

[0136] When a decomposing agent is used for solubilizing the recovered water absorbent resin, the obtained solubilized polymer may contain the decomposing agent. In other words, in the production method (M1), the solubilized polymer may contain a decomposing agent for the water absorbent resin.

[0137] In the manufacturing method (M1), the solubilized polymer may contain an oxidizing agent as a decomposition agent. Here, the oxidizing agent is a compound having oxidizing properties, which generates radicals by heating. Examples of the oxidizing agent include persulfates, such as sodium persulfate, potassium persulfate, and ammonium persulfate; peroxides, such as hydrogen peroxide, alkyl hydroperoxides, and peresters; perchlorates, such as sodium perchlorate and potassium perchlorate; periodates, such as sodium periodate and potassium periodate; percarbonates, perborates, and peracetic acid. The oxidizing agents may be used alone or in combination of two or more. Of these, hydrogen peroxide is preferably used.

[0138] In the manufacturing method (M1), the solubilized polymer may contain a reducing agent as a decomposing agent. The reducing agent is a compound having reducing properties, and generates radicals when used in combination with the above-mentioned oxidizing agent or the below-mentioned compound that generates transition metal ions. Examples of the reducing agent include sulfurous acid (salt), hydrogen sulfite (salt), phosphorous acid (salt), hypophosphorous acid (salt), thiosulfuric acid (salt), formic acid, oxalic acid, erythorbic acid, amines, ascorbic acid (salt) or its derivatives (e.g., L-ascorbic acid (salt), isoascorbic acid (salt), and alkyl esters of ascorbic acid), phosphate esters, and sulfate esters. The reducing agent may be used alone or in combination of two or more. Among these, sulfurous acid (salt), hydrogen sulfite (salt), L-ascorbic acid (salt), and isoascorbic acid (salt) are preferably used.

[0139] In the production method (M1), the solubilizing polymer may contain a transition metal ion as a decomposition agent. Examples of the transition metal ion include Cu. 2+ , Ag + , Fe 2+ , Fe 3+ , Al 3+ , Ni 2+ , Mn 2+ and the like. The transition metal ions may be used alone or in combination of two or more kinds. Examples of compounds that generate the transition metal ions as described above include sulfides, such as ferric sulfate, and the like. Examples of compounds that generate the transition metal ions as described above include chlorides and hydrates thereof, such as ferrous chloride, etc.; organic acid salts and hydrates thereof, such as ferrous fumarate, ferrous oxalate, ferrous chloride, sodium ferrous citrate, ferrous gluconate, ferrous citrate, ferrous acetate, etc.; sulfates and hydrates thereof, such as ferrous sulfate, etc.; and the like.

[0140] In the manufacturing method (M1), the solubilizing polymer may contain an alkaline compound as a decomposing agent. The alkaline compound is a compound that solubilizes the crosslinked portion of the water absorbent resin by alkaline hydrolysis. Examples of such alkaline compounds include hydroxides of alkaline metals such as lithium hydroxide, potassium hydroxide, and sodium hydroxide; hydroxides of alkaline earth metals such as magnesium hydroxide and calcium hydroxide; ammonia; and amine compounds such as aliphatic amines, alicyclic amines, and aromatic amines. The alkaline compounds may be used alone or in combination of two or more.

[0141] When an oxidizing agent is used for solubilizing the recovered water absorbent resin, the resulting solubilized polymer may contain the oxidizing agent. In this specification, the oxidizing agent that the solubilizing agent may contain is also referred to as oxidizing agent (A) for convenience. In other words, in the production method (M1), the solubilized polymer may contain oxidizing agent (A).

[0142] In addition, examples of the method for solubilizing the recovered water absorbent resin include a method for solubilizing the recovered water absorbent resin using chlorine dioxide under acidic conditions (e.g., the method described in JP 2019-108639 A), a method for solubilizing the recovered water absorbent resin using hydrogen peroxide (e.g., the method described in JP 2019-108640 A), and a method for solubilizing the recovered water absorbent resin with ozone-containing ozone water (e.g., the method described in JP 2019-085343 A, etc.).

[0143] The solubilized polymer obtained in the solubilization step may be used in the addition step (A) as it is in the form of an aqueous solution (i.e., it may be added to the reaction system), or it may be dried to form a solid and then used in the addition step (A) (i.e., it may be added to the reaction system).

[0144] In the manufacturing method (M1), the solubilization rate of the solubilized polymer is preferably 50% by mass or more, more preferably 60% by mass or more, even more preferably 70% by mass or more, and particularly preferably 80% by mass or more. This configuration has the advantage of excellent mixability between the solubilized polymer and other raw materials. The solubilization rate of the solubilized polymer can be controlled by adjusting the amount of the decomposition agent used, the decomposition time, the decomposition temperature, the polymer concentration, etc. In addition, in this specification, the method for measuring the solubilization rate of the solubilized polymer will be described in detail in the following examples.

[0145] [1-3-1-8] Crushing process The manufacturing method (M1) preferably further includes a grinding step in which the polymer (e.g., hydrogel) obtained in the polymerization step is ground with a screw extruder such as a kneader or meat chopper, or a grinder such as a cutter mill, to obtain a particulate polymer (hereinafter also referred to as a "particulate polymer"). When kneader polymerization is used as the polymerization form in the polymerization step, the polymerization step and the grinding step are carried out simultaneously. In addition, when a particulate polymer (particulate hydrogel) is directly obtained in the polymerization process, such as in gas phase polymerization or reversed phase suspension polymerization, the grinding step may not be carried out.

[0146] Regarding the grinding conditions and forms other than those described above, the contents disclosed in WO 2011 / 126079 are preferably applied to the present invention.

[0147] [1-3-1-9] Classification process It is preferable that the production method (M1) further includes a classification step of classifying the polymer obtained in the drying step (also referred to as a "dried polymer") to obtain a particulate polymer having a desired particle size (also referred to as a "particulate dried polymer").

[0148] In the classification step, the method for classifying the dried polymer includes sieve classification using a JIS standard sieve (JIS Z8801-1 (2000)), air flow classification, etc. Among them, from the viewpoint of classification efficiency, sieve classification is preferably selected.

[0149] The particle size of the particulate dry polymer obtained in the classification step is not particularly limited, but for example, the mass average particle size (D50) is preferably 200 μm to 500 μm, more preferably 250 μm to 450 μm, and even more preferably 300 μm to 400 μm. The proportion of particles smaller than 150 μm is preferably less than 5% by mass, more preferably 4% by mass or less, and even more preferably 3% by mass or less.

[0150] In the classification step, the dried polymer may be appropriately pulverized to obtain a particulate dried polymer of a desired particle size. The pulverization method is not particularly limited, and a high-speed rotary pulverizer such as a roll mill, a hammer mill, a screw mill, or a pin mill, a vibration mill, a knuckle type pulverizer, or a cylindrical mixer may be used.

[0151] [1-3-1-10] Surface crosslinking process The manufacturing method (M1) preferably further includes a surface cross-linking step, which is a step of providing a portion with a higher cross-linking density on the surface layer (a portion several tens of μm from the surface of the particulate dry polymer) of the particulate dry polymer obtained through the above-mentioned classification step. The surface cross-linking step is composed of a mixing step, a heat treatment step, and a cooling step (optional).

[0152] In the surface cross-linking step, a surface-cross-linked recycled water absorbent resin is obtained by radical cross-linking on the surface of the particulate dried polymer, surface polymerization, a cross-linking reaction with a surface cross-linking agent, etc. Therefore, the particulate dried polymer to be subjected to the surface cross-linking step can also be said to be a recycled water absorbent resin precursor.

[0153] (Surface cross-linking agent) In the surface crosslinking step, it is preferable to crosslink the surface of the particulate dried polymer using a surface crosslinking agent. The surface crosslinking agent is not particularly limited, but may be an organic or inorganic surface crosslinking agent. Among them, from the viewpoint of the physical properties of the recycled water absorbent resin composition, the handling of the surface crosslinking agent, and the like, an organic surface crosslinking agent that reacts with a carboxyl group is preferable. Specifically, as the surface crosslinking agent, one or more compounds disclosed in U.S. Patent No. 7,183,456 can be used. More specifically, as the surface crosslinking agent, polyhydric alcohol compounds, epoxy compounds, haloepoxy compounds, polyvalent amine compounds or condensates thereof with haloepoxy compounds, oxazoline compounds, oxazolidinone compounds, polyvalent metal salts, alkylene carbonate compounds, cyclic urea compounds, and the like can be used. One of these surface crosslinking agents may be used alone, or two or more may be used in combination. In addition, it is preferable to use these surface crosslinking agents in the state of an aqueous solution (i.e., in the state of a surface crosslinking liquid).

[0154] The amount of the surface crosslinking agent used in the surface crosslinking step (the total amount used when a plurality of agents are used) is preferably 0.01 to 10 parts by mass, more preferably 0.01 to 5 parts by mass, relative to 100 parts by mass of the particulate dry polymer. The surface crosslinking agent is preferably added in the form of an aqueous solution, and in this case, the amount of water used is preferably 0.1 to 20 parts by mass, more preferably 0.5 to 10 parts by mass, relative to 100 parts by mass of the particulate dry polymer. Furthermore, a hydrophilic organic solvent may be used in combination as necessary, and in that case, the amount of the hydrophilic organic solvent used is preferably 10 parts by mass or less, more preferably 5 parts by mass or less, relative to 100 parts by mass of the particulate dry polymer. Each additive added in the "re-wetting step" described later can also be mixed into the aqueous solution of the surface crosslinking agent within the range of 5 parts by mass or less.

[0155] (Mixing process) The surface crosslinking step includes a mixing step of mixing the particulate dry polymer with the above-mentioned surface crosslinking agent. The method of mixing the surface crosslinking agent in the mixing step is not particularly limited, but for example, a method of preparing a surface crosslinking agent solution in advance and mixing the solution with the particulate dry polymer by preferably spraying or dropping, more preferably spraying, can be mentioned.

[0156] The device for mixing the particulate dry polymer and the surface crosslinking agent is not particularly limited, but is preferably a high-speed stirring type mixer, more preferably a high-speed stirring type continuous mixer.

[0157] (Heat treatment process) The surface cross-linking step includes a heat treatment step in which the mixture discharged from the mixing step is heated to cause a cross-linking reaction on the surface of the particulate dry polymer. The heat treatment step can also be called a cross-linking reaction step.

[0158] The apparatus for carrying out the heat treatment is not particularly limited, but preferably includes a paddle dryer. The heating temperature in the heat treatment, in other words, the reaction temperature in the crosslinking reaction, is appropriately set according to the type of the surface crosslinking agent used, but is preferably 50°C or more and 300°C or less, more preferably 100°C or more and 200°C or less.

[0159] (cooling process) The surface cross-linking step preferably includes a cooling step of cooling the surface-cross-linked particulate dry polymer after the heat treatment.

[0160] In the cooling step, the cooling device is not particularly limited, but is preferably a device with the same specifications as the device used in the heat treatment step, and more preferably a paddle dryer. This is because it can be used as a cooling device by changing the heat medium to a refrigerant. In addition, the surface crosslinked particulate dry polymer obtained in the heat treatment step is forcibly cooled, if necessary, to preferably 40°C or more and 80°C or less, more preferably 50°C or more and 70°C or less, in the cooling step.

[0161] [1-3-1-11] Crushing (cutting) process The manufacturing method (M1) may further include a crushing (cutting) step of crushing (cutting) used absorbent articles into crushed (cut) materials.

[0162] In the crushing (cutting) step, the method of crushing (cutting) the used absorbent article is not particularly limited, and examples thereof include a method of cutting using a cutting tool such as a cutter, etc. By carrying out the crushing (cutting) step, it is also possible to facilitate separation of each component such as the water-absorbent resin, pulp, nonwoven fabric, etc. from the used absorbent article in the separation step described below.

[0163] In the production method (M1), the timing of performing the crushing (cutting) step is not particularly limited.

[0164] [1-3-1-12] Separation process The manufacturing method (M1) may further include a separation step of separating the water-absorbent resin from a used absorbent article. "Separating the water-absorbent resin from a used absorbent article" refers to taking out the water-absorbent resin that has shrunk by discharging the absorbed liquid from gaps in the pulp, nonwoven fabric, etc. contained in the used absorbent article, and dispersing it in a treatment liquid.

[0165] As a method for separating the water-absorbing resin from the used absorbent article, for example, a method of stirring a mixture of the treatment liquid and the used absorbent article can be mentioned. The water-absorbing resin dispersed in the treatment liquid can be recovered by a conventional solid-liquid separation means for separating soluble and insoluble substances, for example, filtration, centrifugation, etc.

[0166] In the manufacturing method (M1), the timing of carrying out the separation step is not particularly limited. In addition, the above-mentioned crushing (cutting) step and the separation step can be carried out in parallel.

[0167] [1-3-1-13] Other processes The production method (M1) may include, in addition to the above-mentioned respective steps, a washing step of washing the recovered water absorbent resin, a dehydration step of dehydrating the recovered water absorbent resin (preferably, the recovered water absorbent resin after the washing step), a sterilization / disinfection step of sterilizing and / or disinfecting the recovered water absorbent resin (preferably, the recovered water absorbent resin after the washing step), and a regeneration step of imparting (regenerating) sufficient water absorption performance (sufficient for product applications) to the recovered water absorbent resin, and the like.

[0168] Specific aspects of each step of the washing step and the dehydration step will be described in detail in the following sections ([1-3-2-1] Washing step) and ([1-3-2-2] Dehydration step), respectively.

[0169] In the case of a washed recovered water absorbent resin obtained through a washing step and / or a dehydration step as described below, even when a solubilized polymer obtained from the recovered water absorbent resin is used as a part of a raw material, a recycled water absorbent resin composition having an excellent water absorption rate may be obtained. On the other hand, in the conventional technology, a recycled water absorbent resin composition having an inferior water absorption rate is obtained when a recovered water absorbent resin is solubilized without performing a washing step and / or a dehydration step, that is, without washing the recovered water absorbent resin, and the solubilized polymer obtained is used as a part of a raw material. However, the manufacturing method (M1) has an advantage that a recycled water absorbent resin composition having an excellent water absorption rate can be obtained even when a recovered water absorbent resin is solubilized without washing the recovered water absorbent resin, and the solubilized polymer obtained is used as a part of a raw material.

[0170] [1-3-2] Manufacturing method (M2) [1-3-2-1] Cleaning process The manufacturing method (M2) preferably includes a washing step of washing the recovered water absorbent resin. The washing step included in the manufacturing method (M2) can be said to be a step of removing impurities (e.g., body fluids such as human waste, impurities generated during the manufacturing process, etc.) present between particles of the swollen gel of the recovered water absorbent resin, on the particle surfaces, etc., by washing with a washing liquid (washing treatment). Specific washing methods for the recovered water absorbent resin include, for example, a method of adding a washing liquid to the recovered water absorbent resin, a method of immersing the recovered water absorbent resin in a washing liquid, a method of stirring the recovered water absorbent resin while immersing it in a washing liquid, and the like, but are not limited thereto.

[0171] The washing liquid used in the washing step is not particularly limited as long as it is an aqueous liquid that can wash away impurities and does not alter the recovered water absorbent resin, but it is preferable that the recovered water absorbent resin can absorb the washing liquid and swell because it can remove more impurities, especially impurities inside the recovered water absorbent resin. Examples of such washing liquids include deionized water, tap water, distilled water, physiological saline, seawater, etc. Among the above washing liquids, deionized water, tap water, or distilled water is preferable because of its excellent washing effect.

[0172] The temperature of the cleaning liquid in the cleaning step is not particularly limited, and can be from room temperature to 100° C., or steam of the cleaning liquid can be used. When using a high-temperature cleaning liquid or steam of the cleaning liquid of 60° C. or higher, it is preferable because a sterilizing effect can be expected in addition to the cleaning effect.

[0173] The amount of the washing liquid used in the washing step (total amount used) is not particularly limited as long as the recovered water absorbent resin can be sufficiently washed, but for example, it is preferably 2000 parts by mass or more, more preferably 10000 parts by mass or more, and even more preferably 100000 parts by mass or more, relative to 100 parts by mass of the recovered water absorbent resin.

[0174] When the production method (M2) includes a washing step, the washing step needs to be carried out at least once, but may be carried out multiple times.

[0175] [1-3-2-2] Dehydration process The manufacturing method (M2) preferably includes a dehydration step of dehydrating the recovered water absorbent resin, preferably the recovered water absorbent resin after the washing step. The dehydration step can also be said to be a step of dehydrating (dehydrating) the recovered water absorbent resin (preferably the swollen gel of the recovered water absorbent resin) to discharge impurities present inside the water absorbent resin together with moisture to the outside of the system.

[0176] In the dehydration step, the method of dehydrating the recovered water absorbent resin is not particularly limited, and is not particularly limited as long as it is a method capable of reducing the moisture content of the swollen recovered water absorbent resin in a state of absorbing liquid (for example, the aqueous liquid used for washing). Specific dehydration methods include, for example, a method of contacting the swollen gel of the recovered water absorbent resin with various dehydrating liquids such as an aqueous solution containing a hydrophilic organic solvent, an aqueous solution with a low pH (for example, 3 or less), and an aqueous solution of a polyvalent metal salt (for example, calcium chloride), as well as a method of applying a voltage to the swollen gel using a pair of electrodes. Methods of contacting the swollen gel of the recovered water absorbent resin with the various dehydrating liquids include, but are not limited to, a method of adding the liquid to the recovered water absorbent resin gel (swollen gel) in a swollen state, a method of immersing the swollen gel in the liquid, and a method of stirring the swollen gel while immersing it in the liquid.

[0177] In the dehydration step, when the swollen gel of the recovered water absorbent resin is immersed in an aqueous solution containing a hydrophilic organic solvent, the concentration of the hydrophilic organic solvent in the aqueous solution in which the recovered water absorbent resin is immersed is preferably 35% by mass or more, more preferably 40% by mass or more, and even more preferably 45% by mass or more.

[0178] In this specification, the hydrophilic organic solvent refers to an organic solvent having a solubility of 20 g or more in 100 mL of water at 20° C. As the hydrophilic organic solvent, one having a solubility of 25 g or more in 100 mL of water at 20° C. is more preferable, and one having a solubility of 30 g or more in 100 mL of water at 20° C. is even more preferable.

[0179] Specific examples of such hydrophilic organic solvents include: (1) lower alcohols such as methanol, ethanol, n-propyl alcohol, isopropyl alcohol, tert-butyl alcohol, etc.; (2) ketones such as acetone, methyl ethyl ketone, etc.; (3) ethers such as tetrahydrofuran, dioxane, etc.; and (4) esters such as methyl acetate, methyl lactate, ethyl lactate, etc. These hydrophilic organic solvents may be used alone or in combination of two or more.

[0180] In the dehydration step, when the swollen gel of the water-absorbent resin is immersed in an aqueous solution with a low pH (for example, 3 or less), the pH of the aqueous solution is preferably 3 or less, and more preferably 0.5 to 2.5. As the aqueous solution, an aqueous solution containing an acid can be suitably used. As such an acid, either an inorganic acid or an organic acid can be used. In the case of an inorganic acid, for example, hydrochloric acid, sulfuric acid, etc. can be used. In the case of an organic acid, for example, tartaric acid, glycolic acid, malic acid, citric acid, succinic acid, acetic acid, etc. can be used. These acids may be used alone or in combination of two or more.

[0181] In the dehydration step, when the swollen gel of the recovered water absorbent resin is contacted with an aqueous solution of a polyvalent metal salt, examples of the polyvalent metal salt include salts of metals such as calcium, magnesium, aluminum, iron, cobalt, nickel, and copper with chlorine, carbonate, acetate, etc. These polyvalent metal salts may be used alone or in combination of two or more.

[0182] When the manufacturing method (M2) includes a dehydration step, the dehydration step may be carried out at least once, but may be carried out multiple times. When the manufacturing method (M2) includes a washing step in addition to the dehydration step, the dehydration step is preferably carried out after the washing step.

[0183] The production method (M2) may include at least one of the above-mentioned washing step and dehydration step, or may include both the washing step and the dehydration step.

[0184] [1-3-2-3] Drying process The manufacturing method (M2) includes a drying step of drying the recovered water absorbent resin. The drying step is a step of drying the recovered water absorbent resin in a moist state until the resin solid content is a desired value. The resin solid content of the water absorbent resin is determined from the loss on drying of the water absorbent resin (the change in mass before and after heating 1 g of the water absorbent resin at 180° C. for 3 hours), and is preferably 80% by mass or more, more preferably 85% by mass to 99% by mass, even more preferably 90% by mass to 98% by mass, and particularly preferably 92% by mass to 97% by mass.

[0185] In the drying step, the method for drying the recovered water absorbent resin is not particularly limited, but examples thereof include heat drying, hot air drying, reduced pressure drying, fluidized bed drying, infrared drying, microwave drying, drum dryer drying, drying by azeotropic dehydration with a hydrophobic organic solvent, and superheated steam drying using high-temperature steam. Among these, from the viewpoint of drying efficiency, hot air drying is preferred as the drying method, and band drying in which hot air drying is performed on a ventilation belt is more preferred. In addition, in the drying step, only one of these drying methods may be performed, or two or more may be combined and performed.

[0186] When hot air drying is performed in the drying step, the drying temperature (hot air temperature) in the hot air drying is preferably 120°C or more and 250°C or less, more preferably 150°C or more and 200°C or less, from the viewpoint of the color tone and drying efficiency of the obtained recycled water absorbent resin composition. The drying conditions other than the above drying temperature, such as the wind speed of the hot air and the drying time, can be appropriately set according to the moisture content, total mass and target resin solid content of the recovered water absorbent resin to be dried. In addition, when band drying is performed, known drying conditions, for example, conditions described in International Publication Nos. 2006 / 100300, 2011 / 025012, 2011 / 025013, and 2011 / 111657, can be appropriately applied as drying conditions.

[0187] [1-3-2-4] Addition step (E) In this specification, the metal chelating agent used in the addition step (E) is referred to as metal chelating agent (C) for the sake of convenience.

[0188] In the manufacturing method (M2), by adding a metal chelating agent (C) to the recovered water absorbent resin, when the recovered water absorbent resin contains polyvalent metals derived from human waste, the polyvalent metals can be captured, and the presence of the polyvalent metals in the form of ions in the water absorbent resin can be reduced or prevented. As a result, the recycled water absorbent resin composition obtained has an advantage of being excellent in color tone without using a bleaching agent. In addition, by carrying out the addition step (E), the recycled water absorbent resin composition obtained has an advantage of being excellent in water soluble matter and durability. In addition, by carrying out the addition step (E), the recycled water absorbent resin composition obtained has an advantage of being excellent in water absorption performance (for example, water absorption speed) without carrying out excessive purification.

[0189] In actual collection of used absorbent articles, used sanitary materials of various types and manufacturers can be collected without distinction between types and manufacturers. In addition, various manufacturers manufacture various types of water absorbent resins, and the water absorbent resins can be collected from waste generated in the manufacturing process of each of these manufacturers without distinction between types and manufacturers. Therefore, the recovered water absorbent resins may include used water absorbent resins of various manufacturers and various types. In other words, in the manufacturing method (M2), the water absorbent resin (recovered water absorbent resin) may be a water absorbent resin recovered from one or more types of used absorbent articles and / or one or more types of waste generated in the manufacturing process of one or more types of water absorbent resins.

[0190] Conventionally, when a recycled water absorbent resin composition is obtained from recovered water absorbent resins containing various kinds of water absorbent resins from various manufacturers, the water absorption performance of the obtained recycled water absorbent resin composition may not be stable. However, since the manufacturing method (M2) has the addition step (E), even when recycled water absorbent resins derived from various kinds of water absorbent resins from various manufacturers are recycled, it has an advantage that a recycled water absorbent resin composition having excellent color tone, excellent water soluble content and durability, excellent water absorption speed, and little or no odor can be provided.

[0191] Specific examples of the metal chelating agent (C) are the same as those explained in the section "(1-2-5) Metal chelating agents" above, so the explanation therein is incorporated by reference and will not be repeated here.

[0192] Examples of methods for adding the metal chelating agent (C) to the recovered water absorbent resin include, but are not limited to, adding the metal chelating agent (C) as is, adding the metal chelating agent (C) in a solution or slurry state, and the like.

[0193] In the manufacturing method (M2), the timing of performing the addition step (E), i.e., the timing of adding the metal chelating agent (C), is not particularly limited as long as it is after the washing step (if the washing step is performed multiple times, the last washing step) and / or after the dehydration step (if the dehydration step is performed multiple times, the last dehydration step). The addition step (E) can be performed, for example, after the washing step and before the dehydration step, after the washing step and during the dehydration step, before the grinding step described below, during the grinding step, after the grinding step, before the drying step, during the drying step, after the drying step, before the addition step (B) described below, during the addition step (B), after the addition step (B), before the surface cross-linking step described below, during the surface cross-linking step, or after the surface cross-linking step. Since there is an advantage that the deterioration of the recycled water absorbent resin composition can be suppressed, the addition step (E) is preferably performed before the drying step (for example, between the washing step and / or the dehydration step and the drying step), and more preferably during the grinding step. That is, in the manufacturing method (M2), the addition step (E) is preferably performed between the washing step and / or the dehydration step and the drying step, and more preferably during the pulverization step. An example of a method for performing the addition step (E) during the pulverization step is to feed the metal chelating agent (C) together with the recovered water absorbent resin to a pulverizer, and mix the recovered water absorbent resin and the metal chelating agent (C) in the pulverizer while pulverizing the recovered water absorbent resin. An example of a method for performing the addition step (E) during the addition step (B) is to add the metal chelating agent (C) and the inorganic reducing agent together to the recovered water absorbent resin. More specifically, the metal chelating agent (C), the inorganic reducing agent, and water (e.g., deionized water) may be mixed to prepare an aqueous solution, and then the obtained aqueous solution may be added to the recovered water absorbent resin.

[0194] In the manufacturing method (M2), the addition step (E) may be performed at least once, but may be performed multiple times. In the manufacturing method (M2), when the addition step (E) is performed multiple times, from the viewpoint of excellent water absorption properties (particularly water absorption speed) of the recycled water absorbent resin composition, it is preferable to perform the addition step (E) after the washing step and / or dehydration step and before and after the drying step, for example, during the pulverization step and after the surface crosslinking. That is, in the manufacturing method (M2), it is preferable to perform the addition step (E) at least once after the washing step and / or dehydration step and before the drying step, and at least once after the drying step (total of at least two times).

[0195] The amount (addition amount) of the metal chelating agent (C) used in the addition step (E) is not particularly limited, but for example, it is preferably 0.01% by mass or more and 5.0% by mass or less with respect to 100% by mass of the finally obtained recycled water absorbent resin composition, and in the following order, it is preferably 0.01% by mass or more and 2.0% by mass or less, 0.02% by mass or more and 1.0% by mass or less, 0.03% by mass or more and 0.9% by mass or less, 0.04% by mass or more and 0.8% by mass or less, 0.05% by mass or more and 0.7% by mass or less, 0.06% by mass or more and 0.6% by mass or less, and most preferably 0.07% by mass or more and 0.5% by mass or less. When the amount of the metal chelating agent (C) used is 0.01% by mass or more and 5.0% by mass or less with respect to 100% by mass of the recycled water absorbent resin composition, the obtained recycled resin has an advantage that it is excellent in color tone, water soluble matter and durability, and further has an excellent water absorption speed.

[0196] The recovered water absorbent resin may contain one or more polyvalent metal cations selected from the group consisting of, for example, calcium ions, magnesium ions, and aluminum ions. The polyvalent metal cations in the recovered water absorbent resin are, for example, polyvalent metal cations or polyvalent metal salts used in the manufacturing process of the water absorbent resin, or body fluids such as human waste. In addition, when an aqueous solution of a polyvalent metal salt is used in the dehydration step, a part of the polyvalent metal salt may be ionized to generate a polyvalent metal cation. In addition, when a polyvalent metal salt is used in the regeneration step described below, a part of the polyvalent metal salt may be ionized to generate a polyvalent metal cation. In addition, when a polyvalent metal salt is used as a surface crosslinking agent in the surface crosslinking step described below, a part of the polyvalent metal salt may be ionized to generate a polyvalent metal cation. Therefore, the finally obtained recycled water absorbent resin composition may also contain one or more polyvalent metal cations selected from the group consisting of, for example, calcium ions, magnesium ions, and aluminum ions. One of the purposes of adding the metal chelating agent (C) is to capture the polyvalent metal cations in the recycled water absorbent resin composition. Therefore, the amount (addition amount) of the metal chelating agent used in the addition step (E) is preferably set appropriately according to the total mass of the polyvalent metal cations in the finally obtained recycled water absorbent resin composition. The total mass of the polyvalent metal cations in the finally obtained recycled water absorbent resin composition depends on the amount of the polyvalent metal cations contained in the recovered water absorbent resin, the amount of the polyvalent metal cations derived from the polyvalent metal salt used in the manufacturing process of the recycled water absorbent resin composition, etc. The amount (addition amount) of the metal chelating agent (C) used in the addition step (E) is, for example, preferably 2 times or more and 1000 times or less in mass, more preferably 2.5 times or more and 500 times or less in mass, and even more preferably 3 times or more and 100 times or less in mass, relative to the total mass of the polyvalent metal cations in the recycled water absorbent resin composition. When the amount of the metal chelating agent (C) used is 2 times or more and 1000 times or less in mass relative to the total mass of the polyvalent metal cations in the recycled water absorbent resin composition, the obtained recycled resin has the advantage of being excellent in color tone, water soluble content and durability, and also excellent in water absorption speed.The amount of polyvalent metal cations in the recycled water absorbent resin composition can be measured by a method such as ICP emission spectrometry.

[0197] The amount of the metal chelating agent in the finally obtained recycled water absorbent resin composition is preferably 0.01% by mass or more and 5.0% by mass or less, in 100% by mass of the recycled water absorbent resin composition, and is preferably 0.01% by mass or more and 2.0% by mass or less, 0.02% by mass or more and 1.0% by mass or less, 0.03% by mass or more and 0.9% by mass or less, 0.04% by mass or more and 0.8% by mass or less, 0.05% by mass or more and 0.7% by mass or less, 0.06% by mass or more and 0.6% by mass or less, and most preferably 0.07% by mass or more and 0.5% by mass or less. The amount of the metal chelating agent in the finally obtained recycled water absorbent resin composition is preferably 2 times or more and 1000 times or less, more preferably 2.5 times or more and 500 times or less, and even more preferably 3 times or more and 100 times or less, based on the total mass of the polyvalent metal cations in the recycled water absorbent resin composition. The amount of the metal chelating agent in the finally obtained recycled water absorbent resin composition depends on the amount of the metal chelating agent (C) added in the addition step (E) and the amount of the metal chelating agent (B) contained in the recovered water absorbent resin. In addition, the metal chelating agent may be consumed by decomposition or the like in a high temperature environment. Therefore, for example, when the addition step (E) is performed before the drying step, a part of the metal chelating agent (C) may be consumed by decomposition or the like with the drying of the recovered water absorbent resin in the drying step. That is, the entire amount of the metal chelating agent (C) used in the addition step (E) may not be contained in the finally obtained recycled water absorbent resin composition. Therefore, taking into consideration the timing of carrying out the addition step (E), the treatment contents of the recovered water absorbent resin containing the metal chelating agent (C), and the amount of the metal chelating agent (B) contained in the recovered water absorbent resin, it is preferable to set the amount of the metal chelating agent (C) used in the addition step (E) so that the amount of the metal chelating agent in the finally obtained recycled water absorbent resin composition falls within the above-mentioned range.

[0198] [1-3-2-5] Metal chelating agents (B) As described above, the recovered water absorbent resin may contain a metal chelating agent (metal chelating agent (B)). In other words, in the production method (M2), the water absorbent resin recovered from used absorbent articles and / or the water absorbent resin recovered from waste generated in the production process of the water absorbent resin may contain a metal chelating agent (B).

[0199] [1-3-2-6] Addition step (F) It is preferable that the production method (M2) further comprises an adding step (F) of adding an inorganic reducing agent to the recovered water absorbent resin.

[0200] Specific examples of the inorganic reducing agent are the same as those explained in the above section "(1-3-1-5) Addition Step (C)," and therefore the explanation therefor is omitted here.

[0201] Methods for adding the inorganic reducing agent to the recovered water absorbent resin include, for example, a method of adding the inorganic reducing agent as it is, a method of adding the inorganic reducing agent in the form of a solution or a slurry, and the like, but are not limited thereto.

[0202] In the manufacturing method (M2), the timing of performing the addition step (F), i.e., the timing of adding the inorganic reducing agent, is not particularly limited. The addition step (F) can be performed, for example, before the washing step, during the washing step, after the washing step, before the dehydration step, during the dehydration step, after the dehydration step, before the addition step (E), during the addition step (E), after the addition step (E), before the grinding step described below, during the grinding step, after the grinding step, before the drying step, during the drying step, after the drying step, before the surface cross-linking step described below, during the surface cross-linking step, or after the surface cross-linking step. Since the addition step (F) has an advantage that the water absorption properties (particularly the water absorption speed) of the recycled water absorbent resin composition are excellent, it is preferable that the addition step (F) is performed after the washing step and / or the dehydration step. For example, it is preferable that the addition step (F) is performed after the washing step and before the dehydration step, after the washing step and during the dehydration step, or after the washing step and the dehydration step. Moreover, the adding step (F) is more preferably carried out at a timing subsequent to the washing step and / or the dehydration step.

[0203] The amount of inorganic reducing agent used (addition amount) in the addition step (F) is not particularly limited, but is preferably 0.05% by mass or more and 10% by mass or less, and more preferably 0.1% by mass or more and 8% by mass or less, relative to 100 parts by mass of the water absorbent resin. When the amount of inorganic reducing agent used in the addition step (F) is 0.05% by mass or more and 10% by mass or less, relative to 100 parts by mass of the water absorbent resin, there is an advantage that the color tone of the recycled water absorbent resin composition is excellent.

[0204] [1-3-2-7] Crushing process The manufacturing method (M2) preferably includes a grinding step of grinding the recovered water absorbent resin, preferably the recovered water absorbent resin after the washing step, more preferably the recovered water absorbent resin after the washing step and the dehydration step, with, for example, a screw extruder such as a kneader or a meat chopper, or a grinder such as a cutter mill. The grinding step is preferably carried out before the drying step, and specifically, it is preferably carried out between the washing step and the dehydration step, and the drying step. When the manufacturing method (M2) includes a grinding step, it has an advantage that the drying efficiency is improved.

[0205] Regarding the grinding conditions and forms other than those described above, the contents disclosed in WO 2011 / 126079 are preferably applied to the present invention.

[0206] [1-3-2-8] Sterilization / disinfection process The production method (M2) may include a sterilization / disinfection step of sterilizing and / or disinfecting the recovered water absorbent resin, preferably the recovered water absorbent resin after the washing step.

[0207] As a method for sterilizing and / or disinfecting the water absorbent resin, for example, a method of treating the water absorbent resin with a disinfectant solution can be mentioned. The disinfectant solution is not particularly limited, and a known one can be used. For example, sodium hypochlorite aqueous solution, chlorine dioxide aqueous solution, ozone water, hydrogen peroxide water, electrolytic water (acidic electrolytic water), etc. can be mentioned. The sterilization and disinfection are preferably carried out in a tank having an agitator blade, or by convection of the aqueous solution, etc., to efficiently mix the recovered water absorbent resin with the disinfectant solution.

[0208] In the manufacturing method (M2), the timing of carrying out the sterilization / disinfection step is not particularly limited. The sterilization / disinfection step can be carried out before the drying step, for example, in parallel with (1) the washing step and / or the crushing (cutting) step described below, or after (2) the washing step and / or the crushing (cutting) step described below. That is, in the manufacturing method (M2), it is preferable to carry out the sterilization / disinfection step between the washing step and / or the crushing (cutting) step and the drying step.

[0209] [1-2-13] Regeneration process The recovered water absorbent resin subjected to the production method (M2) may have no water absorption performance or may have very low water absorption performance (particularly when the recovered water absorbent resin is a recovered water absorbent resin derived from used absorbent articles). However, by subjecting the recovered water absorbent resin to a regeneration step, it is possible to impart (regenerate) sufficient water absorption performance (sufficient for product applications) to the recovered water absorbent resin.

[0210] The regeneration method of the recovered water absorbent resin in the regeneration step is not particularly limited as long as it restores the water absorption ability of the recovered water absorbent resin. For example, a method of contacting a polyvalent metal salt with a recovered water absorbent resin that has absorbed urine, dehydrating the resin, treating the resin with an acidic solution, neutralizing the resin with an alkali metal salt, and then drying the resin (JP Patent Publication No. 2003-225645); a method of contacting a recovered water absorbent resin that has absorbed urine with a solution containing a hydrophilic organic solvent, dehydrating the resin, and then drying the resin (JP Patent Publication No. 2003-326161); a method of contacting a polyvalent metal salt with a recovered water absorbent resin that has absorbed urine, dehydrating the resin, treating the resin with an aqueous alkali metal salt solution, subjecting the resin to ion exchange treatment, and then drying the resin (JP Patent Publication No. 2013-198862); a method of contacting a recovered water absorbent resin that has absorbed urine with an acidic aqueous solution, dehydrating the resin, neutralizing the resin with an alkali metal salt, and then drying the resin (JP Patent Publication No. 2019-135046, etc.); and other known regeneration methods can be used.

[0211] In the production method (M2), the timing of carrying out the regeneration step is not particularly limited. For example, the regeneration step is preferably carried out after the washing step and / or the dehydration step.

[0212] [1-2-14] Crushing (cutting) process The manufacturing method (M2) may include a crushing (cutting) step of crushing (cutting) used absorbent articles into crushed (cut) materials.

[0213] The specific aspects of the crushing (cutting) step are the same as those explained in the above section “(1-3-1-11) Crushing (cutting) step,” so the explanation is omitted here by incorporating the explanation therein.

[0214] In the manufacturing method (M2), by carrying out the crushing (cutting) step, it is possible to increase the contact opportunity between the recovered water absorbent resin in the absorbent article and the washing water, etc., thereby improving the washing effect and the speed thereof.

[0215] In the manufacturing method (M2), the timing of performing the crushing (cutting) step is not particularly limited. The crushing (cutting) step is preferably performed, for example, after the washing step and / or the dehydration step, but the crushing (cutting) step and the washing step may be performed simultaneously, the crushing (cutting) step and the dehydration step may be performed simultaneously, or the crushing (cutting) step, the washing step and the dehydration step may all be performed simultaneously.

[0216] [1-2-15] Separation process The manufacturing method (M2) may include a separation step of separating the water-absorbent resin from the used absorbent article.

[0217] The specific aspects of the separation step are the same as those described in the above section "(1-3-1-12) Separation step," and therefore the description therein is incorporated by reference and will not be described here.

[0218] In the manufacturing method (M2), the timing of carrying out the separation step is not particularly limited. For example, the separation step is preferably carried out after the washing step and / or the dehydration step. For example, the separation step is more preferably carried out between the washing step and / or the dehydration step and the above-mentioned adding step. In addition, the above-mentioned crushing (cutting) step and the separation step can be carried out in parallel (simultaneously).

[0219] [1-2-16] Other processes In addition to the above-mentioned steps, the production method (M2) may include any steps (other steps) that can be carried out in the production process of a normal water absorbent resin, such as a classification step of classifying the obtained recycled water absorbent resin, a surface cross-linking step of surface cross-linking the obtained recycled water absorbent resin, etc. As specific aspects of the other steps in the production method (M2), for example, the aspects described in the items of the classification step and the surface cross-linking step in the production method (M3) described later can be appropriately adopted.

[0220] [1-3-3] Manufacturing method (M3) In the production method (M3), "production of a water absorbent resin using a monomer constituting a water absorbent resin as a raw material" means a production method of a normal (non-recycled) water absorbent resin using a monomer constituting a water absorbent resin as a raw material, for example, a production method of a normal (non-recycled) water absorbent resin including a polymerization step, a pulverization step, a drying step, a classification step, and a surface cross-linking step. Therefore, one embodiment of the production method (M3) can also be expressed as a production method for a water absorbent resin including a polymerization step, a pulverization step, a drying step, a classification step, and a surface cross-linking step, which includes a washing step of washing the recovered water absorbent resin and / or a dehydration step of dehydrating the recovered water absorbent resin, an addition step (E) of adding a metal chelating agent (C) (excluding a monovalent carboxylic acid (salt) consisting only of CHO and a polyvalent carboxylic acid (salt) consisting only of CHO) to the recovered water absorbent resin, and a drying step of drying the recovered water absorbent resin, in which the addition step (E) is performed after the washing step and / or the dehydration step, and which uses a recycled water absorbent resin composition obtained by a recycling method for a recovered water absorbent resin (i.e., a recycled water absorbent resin composition obtained by the production method (M2)) as a part of a raw material.

[0221] A specific embodiment of the production method (M3) will be described in detail below, taking as an example a method including a polymerization step, a pulverization step, a drying step, a classification step, and a surface crosslinking step.

[0222] [1-3-3-1] Each process Specific aspects of each step of the polymerization step, pulverization step, drying step, classification step and surface crosslinking step are the same as those described in the above sections "(1-3-1-1) Polymerization step", "(1-3-1-8) Pulverization step", "(1-3-1-2) Drying step", "(1-3-1-9) Classification step" and "(1-3-1-10) Surface crosslinking step", and therefore the descriptions therein are incorporated by reference and will not be described here.

[0223] [1-3-3-2] Use of recycled water-absorbent resin composition In the manufacturing method (M3), the recycled water absorbent resin composition obtained in the manufacturing method (M2) is used as a part of the raw material of the obtained water absorbent resin. In the manufacturing method (M3), "using the recycled water absorbent resin composition as a part of the raw material of the obtained water absorbent resin" means that the recycled water absorbent resin composition is added to the water absorbent resin raw material (for example, the monomer aqueous solution, the polymer (hydrous gel), the dried polymer, and / or the particulate dried polymer) in any of the above-mentioned steps, specifically, in any of the steps of the polymerization step, the pulverization step, the drying step, the classification step, and the surface cross-linking step.

[0224] The method of adding the recycled water absorbent resin composition to the water absorbent resin raw material is not particularly limited, and examples thereof include a method of adding the recycled water absorbent resin composition as it is, a method of adding the recycled water absorbent resin composition in a state of a swollen gel obtained by swelling the recycled water absorbent resin composition with water, a method of adding the recycled water absorbent resin composition in a state of being dispersed in water, a method of solubilizing the recycled water absorbent resin composition by a known method and adding it in the state of a solubilized polymer, and the like.

[0225] More specifically, when the recycled water absorbent resin composition is added in the "preparation step of the aqueous monomer solution", the recycled water absorbent resin composition may be added to the aqueous monomer solution, or the recycled water absorbent resin composition may be added to water in advance and then mixed with other raw materials such as monomers. From the viewpoint of uniform mixing of the raw materials, it is preferable to add the recycled water absorbent resin composition to the aqueous monomer solution.

[0226] When the recycled water absorbent resin composition is added in the "polymerization step", the recycled water absorbent resin composition may be added before the start of polymerization, or may be added after the start of polymerization. From the viewpoint of uniformity of the polymer component, it is preferable to add the recycled water absorbent resin composition before the start of polymerization.

[0227] When the recycled water absorbent resin composition is added in the "gel crushing step", the recycled water absorbent resin composition may be added before crushing, or may be added during crushing. It may also be added in portions. From the viewpoint of uniformity of the gel component, it is preferable to add the recycled water absorbent resin composition before gel crushing.

[0228] When the recycled water absorbent resin composition is added in the "gel drying step", the hydrous gel and the recycled water absorbent resin composition may be mixed before drying, or after drying. When the powder of the recycled water absorbent resin composition and the hydrous gel are mixed before drying, the moisture of the hydrous gel is transferred to the recycled water absorbent resin composition powder. Therefore, it is preferable because it is expected to have effects such as shortening the drying speed and reducing the generation of undried gel.

[0229] When the recycled water absorbent resin composition is added in the "classification step", the dried polymer and the recycled water absorbent resin composition may be mixed before or after classification. From the viewpoint of uniformity of particle size, it is preferable to add the recycled water absorbent resin composition before classification.

[0230] When the recycled water absorbent resin composition is added in the "surface cross-linking step", the particulate dried polymer and the recycled water absorbent resin composition may be mixed in advance, or may be treated without mixing. From the viewpoint of uniform mixing of the surface cross-linking liquid and the water absorbent resin composition, it is preferable to use the particulate recycled water absorbent resin composition and subject all the surface cross-linked materials (i.e., the particulate dried polymer and the particulate recycled water absorbent resin composition) to surface cross-linking in the form of particulates.

[0231] In the manufacturing method (M3), the recycled water absorbent resin composition may be added at any of the above-mentioned timings. The entire amount of the recycled water absorbent resin composition to be added may be added at one time at any timing, or may be added in portions at multiple timings. The recycled water absorbent resin composition may be added in different forms depending on the timing of addition.

[0232] In the manufacturing method (M3), the ratio of the recycled water absorbent resin composition to all the water absorbent resin raw materials is not particularly limited, but is preferably 1% by mass or more and 60% by mass or less, more preferably 3% by mass or more and 50% by mass or less, and even more preferably 5% by mass or more and 40% by mass or less. In other words, in the manufacturing method (M3), it is preferable to add the recycled water absorbent resin composition so that the ratio of the recycled water absorbent resin composition to all the water absorbent resin raw materials is within the above range. The above-mentioned "all the water absorbent resin raw materials" refers to all the raw materials used in the manufacturing process of the water absorbent resin (i.e., the total amount of the recycled water absorbent resin composition to be added and the water absorbent resin prepared from the aqueous monomer solution). More specifically, the raw materials include the recycled water absorbent resin composition, and the non-recycled water absorbent resin and its raw materials (e.g., acrylic acid (salt); basic composition; other monomers; internal crosslinking agents; other substances (starch, etc.); polymerization initiators; and surface crosslinking agents, etc.). The above ratio is the ratio of the solid content of the recycled water-absorbent resin composition to the solid content of all the raw materials for the water-absorbent resin.

[0233] [1-4] Physical properties of the recycled water-absorbent resin composition [1-4-1] Color tone of the recycled water absorbent resin composition (yellowness index / YI value) The YI value of the recycled water absorbent resin composition is preferably less than 20.0, more preferably 19.0 or less, more preferably 18.0 or less, even more preferably 17.0 or less, and particularly preferably 16.0 or less. The lower limit of the YI value of the recycled water absorbent resin composition is not particularly limited and may be 0. The YI value of the recycled water absorbent resin composition is an index indicating the color tone of the recycled water absorbent resin composition, and the YI value of the recycled water absorbent resin composition within the above range means that the coloring of the recycled water absorbent resin composition is more suppressed. The YI value of the recycled water absorbent resin composition can be measured by the method described in the examples.

[0234] [1-4-2] Water absorption properties of the recycled water absorbent resin composition The water absorption properties of the recycled water absorbent resin composition are preferably CRC 25.0g / g or more, more preferably 30.0g / g or more, even more preferably 35.0g / g or more, and particularly preferably 36.0g / g or more. Also, AAP (0.3psi) is preferably 12.0g / g or more, more preferably 15.0g / g or more, more preferably 18.0g / g or more, more preferably 20.0g / g or more, more preferably 22.0g / g or more, more preferably 24.0g / g or more, more preferably 26.0g / g or more, more preferably 28.0g / g or more, and particularly preferably 29.0g / g or more. The water absorption speed (Vortex) is preferably less than 56 seconds, more preferably 55 seconds or less, more preferably 54 seconds or less, even more preferably 53 seconds or less, and particularly preferably 52 seconds or less. The CRC, AAP (0.3 psi) and / or water absorption rate (Vortex) of the recycled water absorbent resin composition in the above range means that the recycled water absorbent resin composition has excellent water absorption properties. The CRC, AAP (0.3 psi) and water absorption rate (Vortex) of the recycled water absorbent resin composition can be measured by the method described in the Examples.

[0235] [1-4-3] Water-soluble content of the recycled water-absorbent resin composition The water-soluble content of the recycled water-absorbent resin composition is preferably less than 33% by mass, more preferably 32% by mass or less, more preferably 30% by mass or less, more preferably 25% by mass or less, more preferably 20% by mass or less, more preferably 18% by mass or less, more preferably 17% by mass or less, even more preferably 16% by mass or less, and particularly preferably 15% by mass or less. The lower limit of the water-soluble content of the recycled water-absorbent resin composition is not particularly limited, but is at least greater than 0% by mass. The water-soluble content of the recycled water-absorbent resin composition can be measured by the method described in the Examples.

[0236] [1-5] Others [1-5-1] "EDANA" and "ERT" "EDANA" is an abbreviation for European Disposables and Nonwovens Associations. Also, "ERT" is an abbreviation for EDANA Recommended Test Methods. In one embodiment of the present invention, unless otherwise specified, the physical properties of the water-absorbent resin are measured in accordance with the original ERT (revised in 2002 / publicly known document).

[0237] [1-5-2] Other In this specification, unless otherwise specified, "ppm" means "ppm by mass."

[0238] In this specification, "acid (salt)" means "acid and / or its salt." "(Meth)acrylic" means "acrylic and / or methacrylic."

[0239] In this specification, the unit of volume "liter" may be written as "l" or "L". EXAMPLES

[0240] The present invention will be described in more detail with reference to the following examples and comparative examples. However, the present invention is not limited to these examples. Examples obtained by appropriately combining the technical means disclosed in each example are also included in the scope of the present invention.

[0241] (Measurement and evaluation methods) The methods for measuring and evaluating each physical property in the examples and comparative examples are as follows.

[0242] (a) CRC The "CRC" of a water absorbent resin is an abbreviation for "Centrifuge Retention Capacity" and indicates the absorption capacity (unit: g / g) of a water absorbent resin for 30 minutes under no pressure with respect to a 0.90 mass% sodium chloride aqueous solution. The method for measuring the CRC of a specific water absorbent resin (recycled water absorbent resin composition) was as follows.

[0243] 0.200 g of the water-absorbent resin was uniformly placed in a bag (85 mm x 60 mm) made of nonwoven fabric (manufactured by Nangoku Pulp Kogyo Co., Ltd., product name: Heatlon Paper, model: GSP-22) and heat-sealed. The bag (containing the water-absorbent resin) was immersed in a large excess (usually about 500 ml) of 0.90% by mass sodium chloride aqueous solution at room temperature. After 30 minutes, the bag was pulled out and drained for 3 minutes at a centrifugal force (250 G) described in ERT441.2-02 using a centrifuge (manufactured by Kokusan Co., Ltd., centrifuge: model H-122), and the mass W1 (g) of the bag was measured. In addition, the same operation was performed without using the water-absorbent resin, and the mass W0 (g) at that time was measured. From the measured values ​​of W1 and W0, the CRC of the control water-absorbent resin was calculated according to the following formula (1): CRC of absorbent resin (g / g) = (W1-W0) / (mass of absorbent resin)-1···Equation (1).

[0244] (b) AAP0.3 The "AAP" of a water-absorbent resin is an abbreviation for "Absorption Against Pressure" and indicates the absorbency (unit: g / g) against a 0.90% by mass aqueous sodium chloride solution. Also, "AAP0.3" means the AAP under a pressure of 0.3 psi.

[0245] The AAP0.3 of the above water absorbent resin (recycled water absorbent resin composition) was measured in accordance with ERT442.2-02. Specifically, 0.9 g of the water absorbent resin was placed in a large excess of 0.9 mass % sodium chloride aqueous solution for 1 hour, and the AAP0.3 was measured at 2.07 kPa (21 g / cm 2 The value was measured after swelling under a pressure of 0.5 psi (0.3 psi).

[0246] (c) Water absorption rate (Vortex) 0.02 parts by mass of edible blue No. 1 (CAS number: 3844-45-9), a food additive, was added to 1.000 parts by mass of a 0.90% by mass aqueous sodium chloride solution (physiological saline) prepared in advance, and the liquid temperature was adjusted to 30°C. 50 ml of the physiological saline thus obtained was weighed into a 100 ml beaker with a body diameter of 55 mm and a height of 70 mm, and a cylindrical Teflon (registered trademark) magnetic stirrer with a length of 40 mm and a thickness of 8 mm was placed in the beaker. 2.0 g of water-absorbent resin was added while stirring the physiological saline at 600 rpm, and the water absorption rate (seconds) was measured. The start point of the water absorption rate measurement and the end point of the measurement were in accordance with the standards described in JIS K 7224 (1996) "Explanation of the water absorption rate test method for superabsorbent resins". Specifically, the water-absorbent resin was placed as uniformly as possible near the inner wall surface of the beaker, and then a timer was started (start point). The time (end point) until the saline solution was absorbed by the water-absorbent resin and the gelling saline solution covered the rotating stirrer tip (covered in a V shape when viewed from the cross section) was measured. The obtained time (seconds) was defined as the water absorption rate (seconds).

[0247] (d) Solids concentration of the solubilized polymer aqueous solution In this specification, the solids concentration of the solubilized polymer aqueous solution was measured by the following method. That is, a solubilized polymer aqueous solution with a mass Wa (g) was placed on an aluminum dish with a mass Wb (g) and dried in a hot air circulating oven at 180°C for 3 hours. Thereafter, the total mass Wc (g) of the solubilized polymer and the aluminum dish was measured. The solids concentration of the solubilized polymer aqueous solution was calculated from the obtained values ​​of Wa, Wb, and Wc according to the following formula (3): Solids concentration (mass%) of solubilized polymer aqueous solution = {(mass Wc - mass Wb) / mass Wa} × 100 Equation (3).

[0248] (e) Urea content 200.0 g of 0.9% by mass sodium chloride aqueous solution was weighed out into a plastic container with a capacity of 250 ml and a lid. Next, 1.00 g of water-absorbent resin was added to the sodium chloride aqueous solution, and the mixture was stirred for 16 hours by rotating a stirrer. By this operation, the urea content in the water-absorbent resin was extracted.

[0249] Subsequently, the extract was filtered through a filter (0.45 μm), and the obtained filtrate was analyzed by liquid chromatography (HPLC) to quantitatively determine the amount of urea contained in the water-absorbent resin.

[0250] (f) Color tone The color state of the recycled water absorbent resin composition after drying was visually observed. A water absorbent resin without coloring is white, and a water absorbent resin with coloring due to impurities is yellow. The closer to white the resin is, the better.

[0251] (g) Polyvalent metal cation content in the solubilized polymer Nitric acid was added to the aqueous solution of the solubilized polymer (or the concentrated solution of the solubilized polymer), and the resulting aqueous solution was then repeatedly heated and irradiated with microwaves in stages to obtain decomposition products of the solubilized polymer. The content of polyvalent metal cations in the solubilized polymer was quantified by ICP emission spectroscopy of the decomposition products.

[0252] (h) Color Tone Evaluation (Yellowness Index / YI value) The color tone evaluation (yellowness / YI value) of the water-absorbent resin was performed using a spectrophotometer (Spectrophotometer SE7700) manufactured by Nippon Denshoku Industries Co., Ltd. Reflection measurement was selected as the measurement setting condition, and the measurement diameter was LAV (28 mm). An accessory 35Φ×15H round cell, a 35Φ×15H cell case, and a standard white board for powder were used. About 1.5 g of the water-absorbent resin immediately after production was uniformly filled on the sample stage so that there was no gap on the bottom surface. Under the conditions of room temperature (20°C or higher and 25°C or lower) and humidity of 50 RH%, the YI value (yellowness index; ASTM D1925) in the Hunter Lab color system of the water-absorbent resin immediately after production (recycled water-absorbent resin composition) was measured from the back side of the sample stage using the spectrophotometer.

[0253] (i) Color Tone Evaluation (Color Tone) The color tone (hue) of the water-absorbent resin was evaluated by visual observation. A water-absorbent resin that is not colored is white, and a water-absorbent resin that is colored by impurities is yellow. The closer to white the resin is, the better.

[0254] (j) Water soluble content According to ERT470.1-99, 1.0 g of the water-absorbent resin was stirred in 200 ml of physiological saline for 16 hours, and the water-soluble polymer content (mass%) in the filtrate was determined by pH titration, and the obtained value was taken as the water-soluble content.

[0255] (k) Durability evaluation 20.0 g of physiological saline (at 37°C, simulating body temperature) containing 1.00 g of water-absorbent resin and 0.05% by mass of L-ascorbic acid was added to a sealed container with a capacity of 200 ml, and the container was sealed and allowed to swell 25 times. After 16 hours, the container was tilted 90° to check the state (fluidity) of the gel. If the gel had no fluidity, the durability was rated as "+ (excellent)", if the gel had fluidity, the durability was rated as "- (slightly poor)", and if the gel was in solution, the durability was rated as "-- (poor)". The standards for durability evaluation are shown in Table 1.

[0256] (l) Polyvalent metal cation content in recycled water absorbent resin composition After adding nitric acid to the water absorbent resin, the obtained water absorbent resin was repeatedly heated and irradiated with microwaves in stages to obtain a decomposition product of the water absorbent resin. The polyvalent metal cation content in the water absorbent resin was quantified by performing ICP emission spectroscopy on the obtained decomposition product.

[0257] [Table 1]

[0258] In the durability evaluation, a fluidity of + (excellent) level or higher indicates that the recycled water-absorbent resin composition being evaluated is a recycled water-absorbent resin composition having excellent water-absorbing properties.

[0259] [Production Example 1-1] A reaction solution was prepared by dissolving 0.44 parts by mass of polyethylene glycol diacrylate (molecular weight 523) in 550 parts by mass of a 38% by mass aqueous solution of sodium acrylate (neutralization rate 71 mol%; 200 ppm of p-methoxyphenol was added as a polymerization inhibitor relative to acrylic acid). The reaction solution was degassed for 30 minutes under a nitrogen gas atmosphere.

[0260] The reaction liquid was then fed to a jacketed stainless steel twin-arm kneader having two sigma-type blades with an openable lid, and the gas in the system was replaced with nitrogen gas while maintaining the liquid temperature at 30°C. Next, 0.24 parts by mass of ammonium persulfate and 0.012 parts by mass of L-ascorbic acid were added to the system while stirring the liquid in the kneader, and the polymerization reaction started about 1 minute later. This polymerization was carried out at 30°C or higher and 95°C or lower. After 60 minutes had elapsed since the start of polymerization, a hydrogel-like crosslinked polymer (hereinafter referred to as "hydrogel") was taken out of the system.

[0261] The obtained hydrogel was dried with hot air at 150° C. for 100 minutes. The dried product was then pulverized using a vibration mill. The pulverized product was then classified using JIS standard sieves with mesh sizes of 850 μm and 106 μm. This operation yielded an irregularly pulverized water absorbent resin precursor (S1-1).

[0262] A surface crosslinking agent composition liquid consisting of 0.03 parts by mass of ethylene glycol diglycidyl ether, 1.35 parts by mass of propylene glycol, and 3.15 parts by mass of water was added to 100 parts by mass of the obtained water absorbent resin precursor (S1-1), and the obtained mixture was mixed. Next, the obtained mixture was heat-treated at 100°C for 45 minutes to perform surface crosslinking of the water absorbent resin precursor (S1-1), thereby obtaining a water absorbent resin (S1-1).

[0263] The obtained water absorbent resin (S1-1) had a mass average particle size of 400 μm, a water soluble component amount of 9 mass %, a CRC of 41.7 g / g, an AAP0.3 of 30.7 g / g, and a white color.

[0264] Next, 20.0 g of the water absorbent resin (S1-1) was placed in a beaker, and 600.0 g of artificial urine (a solution consisting of 1.9 mass% urea, 0.80 mass% sodium chloride, 0.10 mass% magnesium chloride hexahydrate, 0.10 mass% calcium chloride dihydrate, and 97.1 mass% ion-exchanged water) was added to the beaker. After that, the beaker was left at room temperature for 24 hours, and the obtained product was used as a simulated used water absorbent resin (1-1).

[0265] [Production Example 1-2] Into a beaker, 620 g of the simulated used water absorbent resin (1-1) obtained in Production Example 1-1 and 1800.0 g of ion-exchanged water were added and stirred for 15 minutes (washing process (water washing treatment: first time)). Then, the contents of the beaker were filtered through a stainless steel wire mesh of 100 mesh (openings 150 μm).

[0266] 1956.5 g of the filtrate obtained by the filtration after the water washing treatment was returned to an empty beaker, and 1900.0 g of acetone was added to the beaker and stirred for 15 minutes (dehydration treatment).Then, the content of the beaker was filtered through a 100 mesh stainless steel wire mesh.

[0267] Next, 104.2 g of the filtrate obtained by the filtration after the dehydration treatment was dried in an oven at 180 ° C. for 3 hours, and then pulverized with a vibration mill. Furthermore, the pulverized material obtained was classified with JIS standard sieves with openings of 850 μm and 106 μm to obtain a recycled water absorbent resin precursor (S1-2) in an irregularly crushed state. The urea content of the recycled water absorbent resin precursor (S1-2) was 1.5 mass%, and the total content of Ca and Mg was about 0.03 mass%.

[0268] (Solubilization process) Separately, 100 g of ion-exchanged water and an appropriate amount of sodium hydroxide were added to 104.2 g of the filtrate after the dehydration treatment to adjust the pH of the mixture to 6.6. Thereafter, the temperature of the mixture was raised to 80° C. while stirring the mixture, and 1.5 g of a 30% by mass aqueous hydrogen peroxide solution was added to the system. This operation started the decomposition (solubilization) of the simulated used water absorbent resin (1-1). After 1 hour had elapsed from the start of the decomposition, the contents of the beaker were filtered through a 100-mesh stainless steel wire mesh. This operation obtained an aqueous solution of the solubilized polymer (1) that had solubilized the simulated used water absorbent resin (1-1) as the filtrate. The mass average molecular weight of the solubilized polymer (1) was 108,000.

[0269] In addition, the insoluble matter remaining on the wire mesh after the filtration (filtrate) was thoroughly washed with ion-exchanged water, and then the insoluble matter together with the wire mesh was dried for 2 hours in an oven at 180° C. Thereafter, the solubilization rate of the solubilized polymer (solubilization rate of the water-absorbent resin) was calculated according to the following formula (4) and was found to be 99.7%.

[0270] Solubilization rate (%) of solubilized polymer = [1 - {(mass of wire mesh and insoluble matter after drying) - (mass of wire mesh)} / (mass of water absorbent resin before decomposition)] × 100 Equation (4).

[0271] The aqueous solution of solubilized polymer (1) was then concentrated using an evaporator to obtain a solubilized polymer concentrate (1) having a solid content of 21.1% by mass.

[0272] [Production Example 1-3] 620 g of the simulated used water absorbent resin (1-1) obtained in Production Example 1-1 and 1800.0 g of ion-exchanged water were added to a beaker and stirred for 15 minutes (water washing treatment: first time). Then, the content of the beaker was filtered through a 100-mesh stainless steel wire screen.

[0273] The filtrate (1956.5 g) obtained by the filtration after the water washing treatment was returned to the empty beaker, and 1800.0 g of fresh ion-exchanged water was added to the beaker and stirred for 15 minutes (water washing treatment: second time).Then, the contents of the beaker were filtered through a 100-mesh stainless steel wire screen.

[0274] 1956.5 g of the filtrate obtained by the filtration after the water washing treatment was returned to an empty beaker, and 1900.0 g of acetone was added to the beaker and stirred for 15 minutes (dehydration treatment).Then, the content of the beaker was filtered through a 100 mesh stainless steel wire mesh.

[0275] Next, 88.1 g of the filtrate obtained after the dehydration treatment was dried in an oven at 180°C for 3 hours, and then pulverized with a vibration mill. The pulverized material obtained was classified with JIS standard sieves with openings of 850 μm and 106 μm to obtain a recycled water absorbent resin precursor (S1-3) in an irregularly crushed state. The urea content of the recycled water absorbent resin precursor (S1-3) was 0.6 mass%, and the total content of Ca and Mg was about 0.01 mass%.

[0276] (Solubilization process) Separately, 104.2 g of the filtrate after the dehydration treatment was subjected to the same operation as in Production Example 1-2 to obtain a solubilized polymer (2). The mass average molecular weight of the solubilized polymer (2) was 108,000.

[0277] Furthermore, the solubilization rate of the solubilized polymer was determined by the same procedure as in Production Example 1-2, and was found to be 99.4%.

[0278] The aqueous solution of solubilized polymer (2) was then concentrated using an evaporator to obtain a solubilized polymer concentrate (2) having a solid content of 21.2% by mass.

[0279] [Comparative Example 1-1] (Polymerization process) A reaction liquid (aqueous monomer solution) was prepared by dissolving 0.42 parts by mass of polyethylene glycol diacrylate (molecular weight: 523) in 522.5 parts by mass of a 38% by mass aqueous solution of sodium acrylate (neutralization rate: 71 mol%) (aqueous monomer solution preparation step).

[0280] Next, the reaction liquid and 50.0 parts by mass of the solubilized polymer concentrate (1) obtained in Production Example 1-2 were added to a jacketed stainless steel twin-arm kneader having two sigma-type blades with an openable lid (addition step (A)), and the gas in the system was replaced with nitrogen gas while maintaining the liquid temperature at 30° C. The solubilized polymer concentrate (1) was added in the form of an aqueous solution at 30° C.

[0281] Next, while stirring the liquid in the kneader, 0.24 parts by mass of ammonium persulfate and 0.012 parts by mass of L-ascorbic acid were added to the system, and the polymerization reaction started about 1 minute later. This polymerization was carried out at 30°C or higher and 95°C or lower. After 60 minutes had passed since the start of the polymerization, the hydrogel (C1-1) was taken out of the system.

[0282] In Comparative Example 1-1, the addition step (A) was carried out during the polymerization step.

[0283] (drying process) The resulting hydrogel (C1-1) was dried with hot air at 170° C. for 30 minutes.

[0284] (Classification process) Thereafter, the dried product was pulverized using a vibration mill. The pulverized product was then classified using JIS standard sieves with mesh sizes of 850 μm and 106 μm. Through this operation, a recycled water absorbent resin composition (C1-1) containing irregularly pulverized water absorbent resin was obtained.

[0285] The recycled water absorbent resin composition (C1-1) thus obtained was colorless and exhibited a white color. The physical properties of the recycled water absorbent resin composition (C1-1) are shown in Table 2.

[0286] [Example 1-1] In Comparative Example 1-1, the same operation as in Comparative Example 1-1 was carried out except that 1000 ppm of trisodium diethylenetriaminepentaacetate was added as a metal chelating agent (A) relative to the monomer solid content (mass) to the reaction liquid before the start of polymerization, to obtain a recycled water absorbent resin composition (1-1) containing an irregularly crushed water absorbent resin. That is, in Example 1-1, the addition step (B) was carried out during the polymerization step. The obtained recycled water absorbent resin composition (1-1) was not colored and was white. The physical properties of the recycled water absorbent resin composition (1-1) are shown in Table 2.

[0287] In Example 1-1, the amount of polyvalent metal cations in the solubilized polymer concentrate (1) was 0.03% by mass relative to the solubilized polymer solid content. Therefore, the amount of the metal chelating agent (A) used in Example 1-1 was 6.3 times by mass relative to the total amount of polyvalent metal cations.

[0288] In Example 1-1, the amount of the metal chelating agent (A) used was 0.095% by mass with respect to 100% by mass of the recycled water absorbent resin (1-1).

[0289] [Comparative Example 1-2] In Comparative Example 1-1, the solubilized polymer concentrate (1) was replaced with the solubilized polymer concentrate (2) obtained in Production Example 1-3, and the same operation as in Comparative Example 1-1 was performed to obtain a recycled water absorbent resin composition (C1-2) containing an irregularly crushed water absorbent resin. The obtained recycled water absorbent resin composition (C1-2) was pale yellow. The physical properties of the recycled water absorbent resin composition (C1-2) are shown in Table 2.

[0290] [Example 1-2] In Comparative Example 1-2, the same operation as in Comparative Example 1-2 was carried out except that 1000 ppm of trisodium diethylenetriaminepentaacetate was added as a chelating agent to the monomer solid content (mass) in the reaction liquid before the start of polymerization, to obtain a recycled water absorbent resin composition (1-2) containing an irregularly crushed water absorbent resin. That is, in Example 1-2, the addition step (B) was carried out during the polymerization step. The obtained recycled water absorbent resin composition (1-2) was not colored and was white. The physical properties of the recycled water absorbent resin composition (1-2) are shown in Table 2.

[0291] In Example 1-2, the amount of polyvalent metal cations in the solubilized polymer concentrate (2) was 0.15% by mass relative to the solubilized polymer solid content. Therefore, the amount of the metal chelating agent used in Example 1-2 was 4.8 times by mass relative to the total amount of polyvalent metal cations.

[0292] In Example 1-2, the amount of the recycled water absorbent resin composition (1-2) obtained was 209.5 parts by mass. Therefore, the amount of the metal chelating agent used was 0.34% by mass relative to 100% by mass of the recycled water absorbent resin composition (1-2).

[0293] [Comparative Example 1-3] (Polymerization process) Into a reaction vessel, 244.9 g of acrylic acid, 0.71 g of polyethylene glycol diacrylate (molecular weight 523) as an internal crosslinking agent (0.040 mol% relative to the carboxyl group-containing unsaturated monomer), 103.7 g of 48.5 mass% aqueous sodium hydroxide solution, further 10 mass% of the aqueous solubilized polymer (1) solution obtained in Production Example 1-2 relative to the monomer solid content (mass), and deionized water in an amount such that the solid content concentration in the aqueous solution is 41 mass% were added and mixed to prepare an aqueous monomer solution (C1-3') (addition step (A)). The solubilized polymer (1) was used in the form of an aqueous solution at 30°C.

[0294] Next, the monomer aqueous solution (C1-3') was cooled while stirring. When the liquid temperature reached 40.0°C, 100.9 g of a 48.5 mass% aqueous sodium hydroxide solution adjusted to 40°C was added and mixed to prepare a monomer aqueous solution (C1-3) (monomer aqueous solution preparation step). At this time, the temperature of the monomer aqueous solution (C1-3) rose to 77.9°C due to the heat of neutralization in the second stage immediately after preparation. Immediately after starting to mix the 48.5 mass% aqueous sodium hydroxide solution, precipitates were observed, but they gradually dissolved to become a transparent homogeneous solution.

[0295] Next, 12.1 g of 4.0 mass% sodium persulfate aqueous solution was added to the stirred monomer aqueous solution (C1-3), and the mixture was immediately poured into a stainless steel bat-shaped container (bottom surface 340 mm x 340 mm, height 25 mm, inner surface; Teflon (registered trademark) coating) in an open-air system. The time from the start of the second stage neutralization to pouring the monomer aqueous solution (C1-3) into the bat-shaped container was 55 seconds, and a hot plate was used as the bat-shaped container, and the surface temperature was heated to 40°C after the monomer aqueous solution (C1-3) was poured. The polymerization reaction started 70 seconds after the monomer aqueous solution (C1-3) was poured into the bat-shaped container. The polymerization reaction proceeded while the reactants expanded and foamed in all directions while generating water vapor. After the reaction, the reactants shrunk to a size slightly larger than the bat-shaped container. After 3 minutes from the start of the polymerization reaction, the reactants were taken out as a hydrous gel (C1-3). This series of operations was carried out in an open atmosphere.

[0296] In Comparative Example 1-3, the addition step (A) was carried out during the polymerization step.

[0297] (Crushing process) The hydrogel (C1-3) obtained by the polymerization reaction was cut into strips, and the gel was crushed with a meat chopper having a die diameter of 7.5 mm.

[0298] (drying process) The crushed hydrogel (C1-3) was spread on a wire net with a mesh size of 50 mesh (opening size of 300 μm) and dried with hot air at 190° C. for 60 minutes.

[0299] (Classification process) Next, the dried product was further pulverized using a vibration mill, and further classified using JIS standard sieves with mesh sizes of 850 μm and 150 μm, to obtain an irregularly pulverized water absorbent resin precursor (C1-3).

[0300] A surface crosslinking agent solution consisting of 0.030 parts by mass of ethylene glycol diglycidyl ether, 1.35 parts by mass of propylene glycol, and 3.15 parts by mass of deionized water was uniformly mixed with 100 parts by mass of the obtained water absorbent resin precursor (C1-3), and the mixture was heat-treated at 100°C for 45 minutes, thereby performing surface crosslinking of the water absorbent resin precursor (C1-3).

[0301] The surface-crosslinked water-absorbent resin precursor (C1-3) was cooled and passed through a JIS standard sieve with a mesh size of 710 μm to obtain a recycled water-absorbent resin composition (C1-3). The physical properties of the obtained recycled water-absorbent resin composition (C1-3) are shown in Table 2.

[0302] [Examples 1-3] A recycled water absorbent resin composition (1-3) was obtained by the same operation as in Comparative Example 1-3, except that 1000 ppm of trisodium diethylenetriaminepentaacetate was added to the reaction vessel as a chelating agent relative to the monomer solid content (mass). That is, in Example 1-3, the addition step (B) was carried out during the polymerization step. The physical properties of the obtained recycled water absorbent resin composition (1-3) are shown in Table 2.

[0303] In Examples 1-3, the amount of polyvalent metal cations in the solubilized polymer (1) was 0.08% by mass relative to the solid content of the solubilized polymer. Therefore, the amount of the metal chelating agent used in Example 3 was 3.7 times the total amount of polyvalent metal cations.

[0304] In Example 3, the amount of the recycled water absorbent resin composition (1-3) obtained was 371.2 parts by mass. Therefore, the amount of the metal chelating agent used was 0.081% by mass relative to 100% by mass of the recycled water absorbent resin composition (1-3).

[0305] [Table 2]

[0306] (summary) Comparison between Comparative Example 1-1 and Example 1-1, and Comparative Example 1-2 and Example 1-2 shows that when a solubilizing polymer is used, the water absorption rate tends to decrease, but when a chelating agent is used, the water absorption rate increases. The present invention can solve the problems of conventional recycled water absorbent resin compositions (such as the decrease in water absorption rate).

[0307] One embodiment of the present invention provides a method for producing a novel recycled water absorbent resin composition using a chelating agent. The recycled water absorbent resin composition according to one embodiment of the present invention is characterized by containing a certain amount or less of a component derived from human waste (urea, polyvalent metal salt, etc.). By containing a certain amount of urea or polyvalent metal salt and a chelating agent, an excellent water absorbent resin can be provided without excessive purification.

[0308] [Reference example 1-1] 620 g of the simulated used water absorbent resin (1-1) obtained in Production Example 1-1 and 1,800.0 g of ion-exchanged water were added to a beaker and stirred for 15 minutes (water washing treatment: first time), and then the content of the beaker was filtered through a 100-mesh stainless steel wire screen.

[0309] 1956.5 g of the filtrate after the water washing treatment obtained in the filtration was returned to the beaker, 1900.0 g of acetone was added thereto, and the mixture was stirred for 15 minutes (dehydration treatment), and then the content of the beaker was filtered through a 100 mesh stainless steel wire screen.

[0310] Next, 104.2 g of the filtrate after the dehydration treatment obtained by the filtration was dried in an oven at 180°C for 3 hours, pulverized in a vibration mill, and further classified using JIS standard sieves with mesh sizes of 850 μm and 106 μm to obtain a recycled water absorbent resin precursor (Reference 1-1) in an irregularly crushed state. The urea content of the recycled water absorbent resin precursor (Reference 1-3) was 1.5 mass%, and the total content of Ca and Mg was about 0.03 mass%.

[0311] [Reference example 1-2] 620 g of the simulated used water absorbent resin (1-1) obtained in Production Example 1-1 and 1,800.0 g of ion-exchanged water were added to a beaker and stirred for 15 minutes (water washing treatment: first time), and then the content of the beaker was filtered through a 100-mesh stainless steel wire screen.

[0312] The filtrate (1,956.5 g) obtained after the water washing treatment in the filtration was returned to the beaker, and 1,800.0 g of fresh ion-exchanged water was added thereto and stirred for 15 minutes (water washing treatment: second time), after which the contents of the beaker were filtered through a 100-mesh stainless steel wire mesh.

[0313] The filtrate (2764.8 g) obtained after the second water washing treatment in the filtration was returned to the beaker, and 2800.0 g of acetone was added thereto and stirred for 15 minutes (dehydration treatment), after which the contents of the beaker were filtered through a 100 mesh stainless steel wire mesh.

[0314] Next, 88.1 g of the filtrate after the dehydration treatment obtained by the filtration was dried in an oven at 180°C for 3 hours, pulverized in a vibration mill, and further classified using JIS standard sieves with mesh sizes of 850 μm and 106 μm to obtain a recycled water absorbent resin precursor (Reference 1-2) in an irregularly crushed state. The urea content of the recycled water absorbent resin precursor (Reference 1-2) was 0.6 mass%, and the total content of Ca and Mg was about 0.01 mass%.

[0315] [Reference example 1-3] 620 g of the simulated used water absorbent resin (1-1) obtained in Production Example 1-1 and 1,800.0 g of ion-exchanged water were added to a beaker and stirred for 15 minutes (water washing treatment: first time), and then the content of the beaker was filtered through a 100-mesh stainless steel wire screen.

[0316] The filtrate (1,956.5 g) obtained after the water washing treatment in the filtration was returned to the beaker, and 1,500.0 g of a 2.7% by mass aqueous citric acid solution was added thereto and stirred for 15 minutes (dehydration treatment), after which the contents of the beaker were filtered through a 100 mesh stainless steel wire mesh.

[0317] 372.8 g of the filtrate after the dehydration treatment obtained in the filtration was returned to the beaker, and 1800.0 g of fresh ion-exchanged water was added thereto and stirred for 15 minutes (water washing treatment: second time), after which the contents of the beaker were filtered through a 100-mesh stainless steel wire mesh.

[0318] The filtrate (606.0 g) obtained after the second water washing treatment was returned to the beaker, and 64.2 g of a 10% by mass aqueous sodium hydroxide solution was added dropwise while stirring the filtrate with a spatula, followed by leaving the mixture to stand for 15 minutes (neutralization treatment).

[0319] Next, the filtered product after the neutralization treatment was dried in an oven at 180°C for 3 hours, pulverized in a vibration mill, and further classified using JIS standard sieves with mesh sizes of 850 μm and 106 μm to obtain a recycled water absorbent resin precursor (Reference 1-3) in an irregularly crushed state. The urea content of the recycled water absorbent resin precursor (Reference 1-3) was 1.7 mass%.

[0320] [Reference example 1-4] 620 g of the simulated used water absorbent resin (1-1) obtained in Production Example 1-1 was dried in an oven at 180°C for 3 hours without washing with water, pulverized in a vibration mill, and further classified with JIS standard sieves with mesh sizes of 850 μm and 106 μm to obtain a recycled water absorbent resin precursor (Reference 1-4) in an irregularly crushed state. The urea content of the recycled water absorbent resin precursor (Reference 1-4) was 29.0 mass%.

[0321] [Reference example 1-5] 620 g of the simulated used water absorbent resin (1-1) obtained in Production Example 1-1 and 1,800.0 g of ion-exchanged water were added to a beaker and stirred for 15 minutes (water washing treatment: first time), and then the content of the beaker was filtered through a 100-mesh stainless steel wire screen.

[0322] Next, 1934.5 g of the filtrate obtained by the filtration after the water washing treatment was dried in an oven at 180°C for 3 hours, pulverized in a vibration mill, and further classified using JIS standard sieves with openings of 850 μm and 106 μm to obtain a recycled water absorbent resin precursor (Reference 1-5) in an irregularly crushed state. The urea content of the recycled water absorbent resin precursor (Reference 1-5) was 24.9 mass%.

[0323] [Reference example 1-6] 620 g of the simulated used water absorbent resin (1-1) obtained in Production Example 1-1 and 1,800.0 g of ion-exchanged water were added to a beaker and stirred for 15 minutes (water washing treatment: first time), and then the content of the beaker was filtered through a 100-mesh stainless steel wire screen.

[0324] The filtrate (1,956.5 g) obtained after the water washing treatment in the filtration was returned to the beaker, and 1,800.0 g of fresh ion-exchanged water was added thereto and stirred for 15 minutes (water washing treatment: second time), after which the contents of the beaker were filtered through a 100-mesh stainless steel wire mesh.

[0325] Next, 2830.3 g of the filtrate obtained after the second water washing treatment was dried in an oven at 180°C for 3 hours, pulverized in a vibration mill, and further classified using JIS standard sieves with mesh sizes of 850 μm and 106 μm to obtain a recycled water absorbent resin precursor (Reference 1-6) in an irregularly crushed state. The urea content of the recycled water absorbent resin precursor (Reference 1-6) was 22.3 mass%.

[0326] [Reference example 1-7] Into a beaker, 620 g of the simulated used water absorbent resin (1-1) obtained in Production Example 1-1 and 1000.0 g of acetone were added and stirred for 15 minutes (dehydration treatment), and then the content of the beaker was filtered through a 100-mesh stainless steel wire screen.

[0327] Next, 102.2 g of the filtrate after the dehydration treatment obtained by the filtration was dried in an oven at 180°C for 3 hours, pulverized in a vibration mill, and further classified using JIS standard sieves with mesh sizes of 850 μm and 106 μm to obtain a recycled water absorbent resin precursor (Reference 1-7) in an irregularly crushed state. The urea content of the recycled water absorbent resin precursor (Reference 1-7) was 3.6 mass%.

[0328] [Reference example 1-8] 620 g of the simulated used water absorbent resin (1-1) obtained in Production Example 1-1 and 1,500.0 g of a 2.7 mass % aqueous citric acid solution were added to a beaker and stirred for 15 minutes (dehydration treatment), and then the content of the beaker was filtered through a 100 mesh stainless steel wire mesh.

[0329] The filtrate (333.4 g) obtained after the dehydration treatment was returned to the beaker, and 2000.0 g of ion-exchanged water was added thereto and stirred for 15 minutes (water washing treatment), after which the contents of the beaker were filtered through a 100-mesh stainless steel wire screen.

[0330] 536.5 g of the filtrate after the water washing treatment obtained by the filtration was placed in a 2000 ml container, and 64.2 g of a 10% by mass aqueous sodium hydroxide solution was added dropwise while stirring the filtrate with a spatula, and then the mixture was allowed to stand for 15 minutes (neutralization treatment).

[0331] Next, the filtered product after the neutralization treatment was dried in an oven at 180°C for 3 hours, pulverized in a vibration mill, and further classified using JIS standard sieves with mesh sizes of 850 μm and 106 μm to obtain a recycled water absorbent resin precursor (Reference 1-8) in an irregularly crushed state. The urea content of the recycled water absorbent resin precursor (Reference 1-8) was 3.0 mass%.

[0332] [Production Example 2-1] A reaction vessel was charged with 244.9 g of acrylic acid, 0.71 g (0.040 mol % relative to the carboxyl group-containing unsaturated monomer) of polyethylene glycol diacrylate (molecular weight 523) as an internal crosslinking agent, 103.7 g of 48.5 mass % aqueous sodium hydroxide solution, and 389.0 g of deionized water, and the mixture was mixed to prepare an aqueous monomer solution (S2-1').

[0333] Next, the monomer aqueous solution (S2-1') was cooled while stirring. When the liquid temperature reached 40.0°C, 100.9 g of a 48.5% by mass aqueous sodium hydroxide solution adjusted to 40°C was added and mixed to prepare a monomer aqueous solution (S2-1). At this time, the temperature of the monomer aqueous solution (S2-1) rose to 78.2°C due to the heat of neutralization in the second stage immediately after preparation. Immediately after starting to mix the 48.5% by mass aqueous sodium hydroxide solution, precipitates were observed, but they gradually dissolved and became a transparent homogeneous solution.

[0334] Next, 12.1 g of 4.0% by mass sodium persulfate aqueous solution was added to the stirred monomer aqueous solution (S2-1), and immediately poured into a stainless steel bat-type container (bottom surface 340×340 mm, height 25 mm, inner surface; Teflon (registered trademark) coating) in an open-air system. The time from the start of the second stage neutralization to pouring the monomer aqueous solution (S2-1) into the bat-type container was 55 seconds, and a hot plate was used as the bat-type container, and the surface temperature was heated to 40° C. after the monomer aqueous solution (S2-1) was poured. The polymerization reaction started 60 seconds after the monomer aqueous solution (S2-1) was poured into the bat-type container. The polymerization reaction proceeded while the reactants expanded and foamed in all directions while generating steam. After the reaction, the reactants shrunk to a size slightly larger than the bat-type container. After 3 minutes had elapsed from the start of the polymerization reaction, the reaction product was taken out as a hydrogel crosslinked polymer (hereinafter referred to as "hydrogel") (S2-1). Note that this series of operations was carried out in an open-to-air system.

[0335] The hydrogel (S2-1) obtained by the polymerization reaction was cut into strips and crushed with a meat chopper having a die diameter of 7.5 mm. The crushed hydrogel (S2-1) was spread on a wire net with a mesh size of 50 mesh (opening size of 300 μm) and dried with hot air at 190° C. for 60 minutes to obtain a dried polymer (S2-1).

[0336] Next, the dried polymer (S2-1) was further pulverized using a vibration mill and further classified using JIS standard sieves with mesh sizes of 850 μm and 150 μm to obtain an irregularly pulverized water-absorbent resin precursor (S2-1).

[0337] A surface crosslinking agent solution consisting of 0.030 parts by mass of ethylene glycol diglycidyl ether, 1.35 parts by mass of propylene glycol, and 3.15 parts by mass of deionized water was uniformly mixed with 100 parts by mass of the obtained water absorbent resin precursor (S2-1), and the mixture was heat-treated at 100°C for 45 minutes, thereby performing surface crosslinking of the water absorbent resin precursor (S2-1).

[0338] The surface-crosslinked water-absorbent resin precursor (S2-1) was cooled and passed through a JIS standard sieve with a mesh size of 710 μm to obtain a water-absorbent resin (S2-1). The obtained water-absorbent resin (S2-1) had a CRC of 35.9 g / g, an AAP0.3 of 29.4 g / g, a YI value (yellowness index) of 10.3, and a water absorption speed (Vortex) of 50 seconds.

[0339] Next, 200 g of the obtained water absorbent resin (S2-1) and 6,000 g of artificial urine (a solution consisting of 1.9 mass% urea, 0.80 mass% sodium chloride, 0.10 mass% magnesium chloride hexahydrate, 0.10 mass% calcium chloride dihydrate, and 97.1 mass% ion-exchanged water) were added to a reaction kettle equipped with a stirrer, and the mixture was left at room temperature for 24 hours to obtain a simulated used water absorbent resin (2-1).

[0340] [Comparative Example 2-1] (Dehydration process) In a reaction vessel equipped with a stirrer, the entire amount of the simulated used water absorbent resin (2-1) obtained in Production Example 2-1 and 10,000 g of ethanol were added, and the mixture was stirred for 15 minutes to carry out a dehydration treatment.

[0341] The simulated used water absorbent resin (C2-1) after the dehydration treatment was filtered through a 100 mesh (150 μm opening) stainless steel wire screen.

[0342] (Crushing process) Next, 800 g of the resulting filtrate after dehydration (corresponding to a solid content concentration of 24.4% by mass and a swelling ratio of approximately 3.1 times) was continuously fed into a meat chopper to crush the gel.

[0343] (drying process) The simulated used water absorbent resin (C2-1) after the gel crushing was dried in an oven at 190° C. for 2 hours.

[0344] (Classification process) Next, the dried simulated used water absorbent resin (C2-1) was pulverized using a vibration mill and further classified using JIS standard sieves with mesh sizes of 850 μm and 106 μm to obtain an irregularly crushed recycled water absorbent resin precursor (C2-1).

[0345] (Surface crosslinking process) 100 parts by mass of the obtained recycled water absorbent resin precursor (C2-1) and a surface crosslinking agent solution consisting of 0.030 parts by mass of ethylene glycol diglycidyl ether, 1.35 parts by mass of propylene glycol, and 3.15 parts by mass of deionized water were uniformly mixed, and the mixture was heated at 100°C for 45 minutes to perform surface crosslinking of the recycled water absorbent resin precursor (C2-1).

[0346] The recycled water absorbent resin precursor (C2-1) after surface cross-linking was cooled and then passed through a JIS standard sieve with a mesh size of 710 μm to obtain a recycled water absorbent resin composition (C2-1).

[0347] The obtained recycled water absorbent resin composition (C2-1) had a CRC of 36.3 g / g, an AAP0.3 of 29.7 g / g, a YI value (yellowness index) of 23.9, a water-soluble content of 16 mass % and a water absorption speed (Vortex) of 60 seconds.

[0348] [Comparative Example 2-2] In the grinding step in Comparative Example 2-1, 10.0 parts by mass of 5.0% hydrogen peroxide aqueous solution (0.50% by mass relative to 100% by mass of absorbent resin) was continuously added to the meat chopper together with 800 g of the filtrate after dehydration treatment as a bleaching agent (100 parts by mass of the filtrate, i.e., 100 parts by mass of the absorbent resin), to obtain a recycled absorbent resin composition (C2-2) by carrying out the same operation as in Comparative Example 2-1. The obtained recycled absorbent resin composition (C2-2) had a CRC of 36.1 g / g, an AAP0.3 of 29.3 g / g, a YI value (yellowness index) of 20.0, a water-soluble content of 17% by mass, and a water absorption speed (Vortex) of 63 seconds.

[0349] [Comparative Example 2-3] In the grinding step in Comparative Example 2-1, 800 g of the filtrate after dehydration treatment was added to the meat chopper continuously with 100 parts by mass of the solid content of the filtrate (i.e., 100 parts by mass of the water absorbent resin), and 10.0 parts by mass of a 30% by mass aqueous hydrogen peroxide solution (3.0% by mass relative to 100% by mass of the water absorbent resin) was added as a bleaching agent. The same operation as in Comparative Example 2-1 was performed to obtain a recycled water absorbent resin composition (C2-3). The obtained recycled water absorbent resin composition (C2-3) had a CRC of 45.2 g / g, an AAP0.3 of 11.8 g / g, a YI value (yellowness index) of 11.3, a water soluble content of 33% by mass, and a water absorption speed (Vortex) of 70 seconds.

[0350] [Example 2-1] In the pulverization step in Comparative Example 2-1, the dehydration step, drying step, classification step and surface crosslinking step were carried out in the same manner as in Comparative Example 2-1, except that an aqueous solution of the metal chelating agent (C) consisting of 0.1 parts by mass of trisodium diethylenetriaminepentaacetate (C) and 4 parts by mass of deionized water was continuously added to the meat chopper together with 800 g of the filtrate after the dehydration treatment and 100 parts by mass of the solid content of the filtrate (i.e., 100 parts by mass of the water absorbent resin) (implementation of the addition step (E)). By such operations, a surface-crosslinked recycled water absorbent resin composition (2-1A) containing 1000 ppm of the metal chelating agent (metal chelating agent (C)) was obtained.

[0351] Then, 100 parts by mass of the recycled water absorbent resin composition (2-1A) was uniformly mixed with an aqueous solution of the metal chelating agent (C) consisting of 0.01 parts by mass of trisodium diethylenetriaminepentaacetate (C) and 1 part by mass of deionized water, and then dried at 60°C for 1 hour.

[0352] Thereafter, the obtained dried product was cooled, and the cooled product was passed through a JIS standard sieve with a mesh size of 710 μm to obtain a recycled water absorbent resin composition (2-1B). The obtained recycled water absorbent resin composition (2-1B) had a CRC of 36.1 g / g, an AAP0.3 of 29.3 g / g, a YI value (yellowness index) of 16.0, a water soluble content of 15 mass%, and a water absorption rate (Vortex) of 50 seconds. Table 3 shows the results of various measurements and evaluations of the recycled water absorbent resin composition (2-1B).

[0353] In Example 2-1, the amount of polyvalent metal cations in the finally obtained recycled water absorbent resin composition (2-1B) was 0.03 mass %. Therefore, the amount of the metal chelating agent (C) used in Example 2-1 was 3.7 times the total amount of the polyvalent metal cations.

[0354] In Example 2-1, the amount of the metal chelating agent (C) used was 0.11% by mass relative to 100% by mass of the recycled water absorbent resin composition (2-1B).

[0355] [Example 2-2] In the grinding process of Comparative Example 2-1, when the filtrate after dehydration treatment was put into the meat chopper to grind the gel, a chelating agent aqueous solution consisting of 0.2 parts by mass of trisodium diethylenetriaminepentaacetate and 4 parts by mass of deionized water was continuously put into the meat chopper with respect to 100 parts by mass of the solid content of the filtrate, except that the dehydrating process, grinding process, classification process and surface cross-linking process were carried out in the same manner as in Comparative Example 2-1. By such operations, a surface-cross-linked recycled water absorbent resin composition (2-2A) containing 2000 ppm of a metal chelating agent (metal chelating agent (C)) was obtained.

[0356] Then, 100 parts by mass of the recycled water absorbent resin composition (2-2A) was uniformly mixed with an aqueous solution of the metal chelating agent (C) consisting of 0.01 parts by mass of trisodium diethylenetriaminepentaacetate (C) and 1 part by mass of deionized water, and then dried at 60°C for 1 hour.

[0357] Thereafter, the obtained dried product was cooled, and the cooled product was passed through a JIS standard sieve with a mesh size of 710 μm to obtain a recycled water absorbent resin composition (2-2B). The obtained recycled water absorbent resin composition (2-2B) had a CRC of 36.0 g / g, an AAP0.3 of 28.9 g / g, a YI value (yellowness index) of 14.7, a water soluble content of 15 mass%, and a water absorption rate (Vortex) of 49 seconds. Table 3 shows the results of various measurements and evaluations of the recycled water absorbent resin composition (2-2B).

[0358] In Example 2-2, the amount of polyvalent metal cations in the finally obtained recycled water absorbent resin composition (2-2B) was 0.03% by mass. Therefore, the amount of the metal chelating agent (C) used in Example 2-2 was 7.0 times by mass relative to the total amount of the polyvalent metal cations.

[0359] In Example 2-2, the amount of the metal chelating agent (C) used was 0.21% by mass relative to 100% by mass of the recycled water absorbent resin composition (2-2B).

[0360] [Example 2-3] In Example 2-1, the aqueous solution of the metal chelating agent (C) added after the surface cross-linking step was changed to an aqueous solution of an inorganic reducing agent consisting of 0.02 parts by mass of sodium sulfite, which is an inorganic reducing agent, and 1 part by mass of deionized water (implementation of the adding step (F)), and the same operation as in Example 2-1 was performed to obtain a recycled water absorbent resin composition (2-3B). The obtained recycled water absorbent resin composition (2-3B) had a CRC of 36.2 g / g, an AAP0.3 of 29.0 g / g, a YI value (yellowness index) of 15.5, a water-soluble content of 15 mass%, and a water absorption speed (Vortex) of 50 seconds. Table 3 shows various measurements and evaluation results for the recycled water absorbent resin composition (2-3B).

[0361] In Example 2-3, the amount of polyvalent metal cations in the finally obtained recycled water absorbent resin composition (2-3B) was 0.03 mass%. Therefore, the amount of the metal chelating agent (C) used in Example 2-3 was 3.3 times the total amount of the polyvalent metal cations.

[0362] In Example 2-3, the amount of the metal chelating agent (C) used was 0.10% by mass with respect to 100% by mass of the recycled water absorbent resin composition (2-3B).

[0363] [Table 3]

[0364] (summary) The recycled water absorbent resin composition (C2-1) of Comparative Example 2-1 has a poor (large) YI value (Yellow-Index) and shows yellowing, which reminds of remaining urine and is not preferable from the viewpoint of hygiene. Therefore, in Comparative Examples 2-2 and 2-3, 0.05% by mass (Comparative Example 2-2) and 3.0% by mass (Comparative Example 2-3) of bleaching agent were added when drying the hydrogel. As a result, in Comparative Example 2-2, yellowing occurs, the YI value is high, that is, the color tone is not improved, and it is understood that the amount of bleaching agent used is insufficient. On the other hand, in Comparative Example 2-3, since a large amount of bleaching agent was used, the YI value became small and the color became white, that is, the color tone was improved, but since the bleaching agent itself is also a decomposition agent for the water absorbent resin, it is understood that the recycled water absorbent resin composition has a significantly increased water-soluble content and has poor durability. That is, if the amount of bleaching agent used is small, the color tone is not improved, whereas if the amount of bleaching agent used is large enough to improve the color tone (i.e., to exhibit a sufficient bleaching effect), the water absorbent resin has poor water-soluble matter and is poor in durability.

[0365] As shown in Examples 2-1 to 2-3, by using a metal chelating agent instead of a bleaching agent, the color became almost white with a clean feeling, that is, the color tone was excellent, and the water-soluble matter did not increase, and the recycled water-absorbent resin composition was excellent in durability. Moreover, in Examples 2-1 to 2-3, the water absorption speed was also improved.

[0366] From the above, it is understood that the addition of a metal chelating agent can solve the various problems (coloration, decrease in water absorption rate, deterioration, etc.) of conventional recycled water-absorbent resin compositions. [Industrial Applicability]

[0367] According to one aspect of the present invention, a recycled water absorbent resin composition having an excellent water absorption rate can be provided. In addition, the recycled water absorbent resin composition according to one embodiment of the present invention has an advantage that it is excellent in color tone (e.g., YI value and color, etc.), water soluble content, and durability, and preferably has little or no odor. Therefore, the recycled water absorbent resin composition according to one embodiment of the present invention can be suitably used for various applications, particularly for sanitary products such as paper diapers, sanitary napkins, and adult incontinence products.

Claims

1. A recycled water-absorbent resin composition, (i) a water-absorbing resin; (ii) based on 100% by mass of the recycled water absorbent resin composition, (ii-1) 0.001% by mass or more and 1.0% by mass or less of one or more polyvalent metal cations selected from the group consisting of calcium ions, magnesium ions, and aluminum ions; and (ii-2) A recycled water absorbent resin composition comprising: 0.01% by mass or more and 5.0% by mass or less of a metal chelating agent (excluding a monovalent carboxylic acid (salt) consisting of only CHO and a polyvalent carboxylic acid (salt) consisting of only CHO).

2. The recycled water-absorbent resin composition according to claim 1 , wherein the water-absorbent resin comprises a plurality of types of water-absorbent resins.

3. 2. The recycled water absorbent resin composition according to claim 1, wherein the content of the metal chelating agent is from 2 times to 1000 times the total mass of the polyvalent metal cations.

4. The recycled water-absorbing resin composition according to any one of claims 1 to 3, further comprising p-methoxyphenol.

Citation Information

Patent Citations

  • Method for regenerating highly water-absorbing polymer, method for producing highly water-absorbing recycled polymer, and use of alkali metal ion source

    WO2019151538A1

  • Method for recycling superabsorbent polymer derived from used absorbent article and recycled superabsorbent polymer derived from used absorbent article

    WO2020241025A1

  • Method for producing highly water-absorbing recycled polymer, and highly water-absorbing recycled polymer

    WO2021205780A1

  • Method for producing secondarily dehydrated highly-water-absorbent polymer for highly-water-absorbent recycled polymer, and method for producing highly-water-absorbent recycled polymer

    WO2023007871A1